Decorative enamel for automotive glass and associated method

By depositing low CTE additive components and glass flux matrix on borosilicate glass, forming a porous decorative layer, the mechanical performance degradation caused by the difference in thermal expansion coefficients of enamel and borosilicate glass is solved, and the excellence of automotive glass is achieved Mechanical and appearance performance.

CN119212957APending Publication Date: 2024-12-27CORNING INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041225.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-29
Filing Date
2023-05-02
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The difference in thermal expansion coefficient between borosilicate glass and commercially purchased ceramic enamels leads to a decrease in the mechanical properties of automotive glass, and the existing enamels are incompatible with low CTE glass, affecting appearance and strength.

Method used

A porous decorative enamel was developed to ensure the mechanical strength and appearance properties of the glass by depositing low CTE additive components and glass flux matrix on borosilicate glass.

Benefits of technology

It improves the mechanical properties and appearance performance of automotive glass, avoids the problem of enamel reducing the strength of glass, and is compatible with borosilicate glass, achieving excellent decorative and functional effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212957A_ABST
    Figure CN119212957A_ABST
Patent Text Reader

Abstract

A decorative glass article includes a glass substrate, a first major surface, and a second major surface disposed opposite the first major surface. The decorative glass article includes a decorative layer adhered to at least a portion of the second major surface. The decorative layer includes a glass flux matrix and a plurality of pores such that the decorative layer exhibits a porosity of at least 5%. The porosity of the decorative layer advantageously prevents the decorative layer from decreasing the mechanical strength of the glass substrate while also providing optical performance attributes suitable for a variety of decorative applications (e.g., shields for use in automotive glazing).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority under 35 U.S.C. §119 to U.S. Provisional Application Serial No. 63 / 343,226 filed on May 18, 2022 and U.S. Provisional Application Serial No. 63 / 428,536 filed on November 29, 2022, the contents of which are the basis of this application and are incorporated herein by reference in their entirety. Technical Field

[0003] The present application relates to decorative enamels for automotive glass, and more particularly to porous decorative enamels. Background Art

[0004] Enamel layers are commonly used as decorative and tinted components of automotive glass (e.g., windshields, sunroofs, and rear windows). As decoration, enamels are usually in the form of dot gradients and borders along the perimeter of the window glass. For example, the decorative layer can both enhance the appearance and protect the underlying adhesive from degradation by ultraviolet rays.

[0005] Automotive glass is conventionally formed from heat-tempered soda-lime-silica glass. Heat tempering produces surface compressive stresses that strengthen the glass's resistance to mechanical breakage. However, the stresses and inherent risks of the road require that conventional automotive glass be relatively thick and heavy to achieve the desired level of durability. Because of this, soda-lime-silica glass tends to have some disadvantages from a durability perspective. Examples of such disadvantages of soda-lime-silicates include poor chemical weathering performance, impact performance, and scratch performance.

[0006] Borosilicate glass is considered for automotive window applications because it has a variety of advantages over soda-lime-silica glass, including improved chemical weathering performance, improved scratch resistance, improved impact performance, and advantageously low density. One complexity associated with borosilicate glass is that the coefficient of thermal expansion ("CTE") of such glass tends to be lower than that associated with soda-lime-silica glass or aluminosilicate glass. This lower coefficient of thermal expansion associated with borosilicate glass may be incompatible with commercially available ceramic enamels. The difference in CTE between borosilicate glass and commercially available enamels may reduce the mechanical properties of the windshield and prevent the windshield from having a desired appearance.

[0007] Therefore, there is a need for an improved enamel for use in combination with borosilicate glass or other suitable low CTE materials. Summary of the invention

[0008] The present disclosure provides decorative enamels suitable for use with borosilicate glass. The decorative enamels described herein advantageously provide a relatively low coefficient of thermal expansion (e.g., at 10×10 -7 K -1 When deposited on borosilicate glass, the decorative enamels described herein further exhibit advantageous mechanical performance attributes because the decorated glass articles can exhibit mechanical strength properties comparable to or even better than those associated with undecorated glass articles. The decorative enamels described herein do not reduce the strength of the glass.

[0009] Aspect (1) of the present disclosure relates to a decorative glass article, comprising: a glass substrate comprising less than or equal to 55×10 -7 K -1 a first major surface, and a second major surface disposed opposite the first major surface; and a decorative layer adhered to at least a portion of the second major surface, the decorative layer comprising: a glass flux matrix, a plurality of low CTE additive component particles, and a plurality of pores, wherein: the decorative layer comprises greater than 15 weight percent of the low CTE additive component particles, each of the plurality of low CTE additive component particles comprises less than or equal to 10×10 -7 K -1 The CTE of the decorative layer is 15×10 of the CTE of the glass substrate. -7 K -1 Inside.

[0010] Aspect (2) of the present disclosure relates to the decorative glass article according to aspect (1), wherein the decorative glass article has a probability of breakage of less than 10% when subjected to a ring-to-ring test with a ring diameter of 32 mm under a load of 60 MPa.

[0011] Aspect (3) of the present disclosure relates to the decorative glass article according to any one of aspects (1) to (2), wherein the CTE of the decorative layer is less than or equal to 55×10 -7 K -1 .

[0012] Aspect (4) of the present disclosure relates to a decorative glass article according to any one of aspects (1)-(3), wherein each of the plurality of low CTE additive component particles comprises glass, glass frit, glass enamel, ceramic enamel, glass ceramic, or ceramic material.

[0013] Aspect (5) of the present disclosure relates to the decorative glass article according to any one of aspects (1) to (4), wherein the decorative layer comprises greater than or equal to 20 wt % and less than or equal to 40 wt % of the low CTE additive component particles.

[0014] Aspect (6) of the present disclosure relates to the decorative glass article according to any one of aspects (1) to (5), wherein the decorative layer comprises greater than or equal to 5 wt % and less than or equal to 30 wt % of pigment.

[0015] Aspect (7) of the present disclosure relates to the decorative glass article according to any one of aspects (1) to (6), wherein the decorative glass article exhibits an L* value according to the CIELAB color coordinate system of less than 15.0 when illuminated from the first major surface using a D65 illumination source.

[0016] Aspect (8) of the present disclosure relates to the decorative glass article according to aspect (7), wherein the L* value is less than or equal to 10.0.

[0017] Aspect (9) of the present disclosure relates to a decorative glass article according to any one of aspects (1) to (8), wherein the decorative glass article exhibits an integrated visible light transmittance of less than or equal to 2.0% for light of 400 nm to 700 nm normally incident on the first major surface in the region where the decorative layer covers the second major surface.

[0018] Aspect (10) of the present disclosure relates to the decorative glass article according to aspect (9), wherein the integrated visible light transmittance is less than or equal to 1.0%.

[0019] Aspect (11) of the present disclosure relates to the decorated glass article according to any one of aspects (1) to (10), wherein the decorative layer comprises an average thickness of less than or equal to 20 μm.

[0020] Aspect (12) of the present disclosure relates to the decorative glass article according to any one of aspects (1) to (11), wherein at least one of the plurality of pores comprises a maximum diameter greater than 1.0 μm.

[0021] Aspect (13) of the present disclosure relates to the decorative glass article according to any one of aspects (1) to (12), wherein the glass substrate is a curved sheet having a concave surface and a convex surface, and the decorative layer is adhered to the concave surface.

[0022] Aspect (14) of the present disclosure relates to the decorative glass article according to any one of aspects (1) to (13), wherein the glass flux matrix comprises an oxide of Bi, B, Zn, Si, or any combination thereof.

[0023] Aspect (15) of the present disclosure relates to a decorative glass article according to any one of aspects (1) to (14), wherein: the glass substrate is formed of a borosilicate glass composition, and in terms of constituent oxides, the borosilicate glass composition includes: SiO2, B2O3, Al2O3, one or more alkali metal oxides, and one or more divalent cation oxides selected from the group consisting of MgO, CaO, SrO, BaO, and ZnO, greater than or equal to 11 mol% and less than or equal to 16 mol% of B2O3, greater than or equal to 2 mol% and less than or equal to 6 mol% of Al2O3, and greater than or equal to 1 mol% and less than or equal to 6 mol% of ZnO. The total amount of Na2O, K2O, MgO, and CaO equal to 7.0 mol%, the concentration based on the mole percentage of the oxides of SiO2, B2O3, one or more alkali metal oxides, Al2O3, and one or more alkaline earth metal oxides satisfies the following relationship: (R2O+R'O)≧Al2O3, 0.80<(1-[(2R2O+2R'O) / (SiO2+2Al2O3)+2B2O3)])<0.93, and wherein R2O is the sum of the concentrations of one or more alkali metal oxides, and R'O is the sum of the concentrations of one or more alkaline earth metal oxides.

[0024] Aspect (16) of the present disclosure relates to the decorative glass article according to any one of aspects (1) to (15), wherein the decorative layer comprises a glass softening temperature of less than or equal to 650°C.

[0025] Aspect (17) of the present disclosure relates to the decorative glass article according to any one of aspects (1) to (16), wherein the thickness of the glass substrate ranges from 2.0 mm to 6.0 mm.

[0026] Aspect (18) of the present disclosure relates to a glass laminate, comprising: a first glass substrate having a first major surface and a second major surface, the first glass substrate comprising less than or equal to 50×10 -7 K -1 The invention relates to a method for manufacturing a glass substrate having a first decorative layer, wherein the first decorative layer comprises a borosilicate glass having a coefficient of thermal expansion (“CTE”) of greater than 15 wt %; a second glass substrate having a third major surface and a fourth major surface; an intermediate layer contacting the second major surface of the first glass substrate and the third major surface of the second glass substrate; and a first decorative layer adhered to at least a portion of the second major surface of the first glass substrate and contacting the intermediate layer, the first decorative layer comprising: a glass flux matrix, a plurality of low CTE additive component particles, and a plurality of pores, wherein: the first decorative layer comprises greater than 15 wt % of the low CTE additive component particles, each of the plurality of low CTE additive component particles comprises less than or equal to 10×10 -7 K -1 The CTE of the additive is 15×10 of the CTE of the first glass substrate.-7 K -1 Inside.

[0027] Aspect (19) of the present disclosure relates to the glass laminate according to aspect (18), wherein the second glass substrate is formed of glass having a second composition that is different from a first composition forming the first glass substrate.

[0028] Aspect (20) of the present disclosure relates to a glass laminate according to any one of aspects (18)-(19), wherein the second composition comprises a soda-lime silicate composition, an aluminosilicate glass composition, an alkali aluminosilicate glass composition, an alkali-containing borosilicate glass composition, an alkali aluminophosphosilicate glass composition, or an alkali aluminoborosilicate glass composition.

[0029] Aspect (21) of the present disclosure relates to a glass laminate according to any one of aspects (18) to (20), wherein the first glass substrate is not chemically strengthened by ion exchange and the second glass substrate is strengthened by ion exchange.

[0030] Aspect (22) of the present disclosure relates to a glass laminate according to any one of aspects (18)-(21), wherein the first glass substrate comprises a first thickness in a range of 2.0 mm to 6.0 mm, and the second glass substrate comprises a second thickness in a range of 0.1 mm to 1.6 mm.

[0031] Aspect (23) of the present disclosure relates to a glass laminate according to any one of aspects (18) to (22), the glass laminate further comprising a second decorative layer adhered to at least a portion of the third major surface of the second glass substrate and contacting the interlayer, wherein a second CTE of the second decorative layer is within 10×10 of a CTE of the second glass substrate. -7 K -1 Inside.

[0032] Aspect (24) of the present disclosure relates to the glass laminate according to any one of aspects (18)-(23), wherein the intermediate layer is disposed in at least one of the plurality of holes in the first decorative layer.

[0033] Aspect (25) of the present disclosure relates to the glass laminate according to any one of aspects (18) to (24), wherein the first CTE of the first decorative layer is less than or equal to 55×10 -7 K -1 .

[0034] Aspect (26) of the present disclosure relates to a glass laminate according to any one of aspects (18)-(25), wherein each of the plurality of low CTE additive component particles comprises glass, glass frit, glass enamel, ceramic enamel, glass ceramic, or ceramic material.

[0035] Aspect (27) of the present disclosure relates to a glass laminate according to any one of aspects (18)-(26), wherein the first decorative layer comprises greater than or equal to 20 wt % and less than or equal to 40 wt % of the low CTE additive component particles.

[0036] Aspect (28) of the present disclosure relates to the glass laminate according to any one of aspects (18)-(27), wherein the first decorative layer includes greater than or equal to 5 wt % and less than or equal to 30 wt % of the pigment.

[0037] Aspect (29) of the present disclosure relates to a glass laminate according to any one of aspects (18)-(28), wherein the glass laminate exhibits an L* value according to the CIELAB color coordinate system of less than 15.0 when illuminated from the first major surface using a D65 illumination source.

[0038] Aspect (30) of the present disclosure relates to a glass laminate according to any one of aspects (18)-(29), wherein the glass laminate exhibits an integrated visible light transmittance of less than or equal to 2.0% for light of 400 nm to 700 nm normally incident on the first major surface.

[0039] Aspect (31) of the present disclosure relates to a glass laminate according to any one of aspects (19) to (30), wherein: the first glass substrate is formed of a borosilicate glass composition, and in terms of constituent oxides, the borosilicate glass composition includes: SiO2, B2O3, Al2O3, one or more alkali metal oxides, and one or more divalent cation oxides selected from the group consisting of MgO, CaO, SrO, BaO, and ZnO, greater than or equal to 11 mol% and less than or equal to 16 mol% of B2O3, greater than or equal to 2 mol% and less than or equal to 6 mol% of Al2O3, and greater than or equal to 1 mol% and less than or equal to 6 mol% of ZnO. The total amount of Na2O, K2O, MgO, and CaO is greater than or equal to 7.0 mol%, and the concentrations calculated as mole percentages of oxides based on SiO2, B2O3, one or more alkali metal oxides, Al2O3, and one or more alkaline earth metal oxides satisfy the following relationship: (R2O+R'O)≧Al2O3, 0.80<(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])<0.93, and wherein R2O is the sum of the concentrations of the one or more alkali metal oxides, and R'O is the sum of the concentrations of the one or more alkaline earth metal oxides.

[0040] Aspect (32) of the present disclosure relates to a method of making a glass article, comprising the steps of: depositing a mixture comprising a ceramic enamel and a low CTE additive component onto a glass substrate to provide a decorative layer; and curing the decorative layer at a temperature greater than a glass softening temperature of the decorative layer to provide a cured decorative layer, the cured decorative layer comprising a plurality of pores and comprising less than or equal to 55×10 -7 K -1 And on the glass substrate 10×10 -7 K -1 The coefficient of thermal expansion (CTE) inside.

[0041] Aspect (33) of the present disclosure relates to the method according to aspect (32), wherein the mixture comprises 40 wt % to 85 wt % of the ceramic enamel and greater than 15 wt % of the low CTE additive component.

[0042] Aspect (34) of the present disclosure relates to the method according to aspect (33), wherein the mixture comprises 20 wt % to 40 wt % of the low CTE additive component.

[0043] Aspect (35) of the present disclosure relates to a method according to any one of aspects (32)-(34), wherein the mixture comprises 5 wt % to 30 wt % of a pigment such that when irradiated using a D65 radiation source, the cured decorative layer exhibits an L* value less than or equal to 10.0.

[0044] Aspect (36) of the present disclosure relates to a method according to any one of aspects (32)-(35), further comprising the step of shaping the glass substrate so that the glass substrate includes a recessed surface and the decorative layer is deposited on the recessed surface.

[0045] Aspect (37) of the present disclosure relates to the method according to aspect (36), wherein curing of the glass substrate and the decorative layer occurs during forming.

[0046] Aspect (38) of the present disclosure relates to a decorative glass article, comprising: a glass substrate including a first major surface and a second major surface disposed opposite the first major surface; a decorative layer adhered to at least a portion of the second major surface, the decorative layer comprising: a glass flux matrix; and a plurality of pores, wherein: a porosity of the decorative layer is greater than or equal to 25% and less than or equal to 30%; a thickness of the glass substrate is greater than or equal to 2.1 mm; a coefficient of thermal expansion ("CTE") of the decorative layer is within 23×10 of the CTE of the glass substrate; -7 K -1and the decorative glass articles exhibit a B5 value greater than or equal to 55 MPa when a ring-to-ring strength test is performed on at least ten of the decorative glass articles in accordance with ASTM C-1499-03.

[0047] Aspect (39) of the present disclosure relates to the decorative glass article according to aspect (38), wherein the glass substrate is formed of a soda-lime-silicate glass composition.

[0048] Aspect (40) of the present disclosure relates to the decorative glass article according to any one of aspects (38)-(39), wherein the glass substrate is not chemically strengthened.

[0049] Aspect (41) of the present disclosure relates to the decoration according to any one of aspects (38) to (40), wherein the difference between the CTE of the decoration layer and the CTE of the glass substrate is greater than or equal to 15×10 -7 K -1 .

[0050] Aspect (42) of the present disclosure relates to a decorative article according to any one of aspects (38)-(41), wherein the decorative layer comprises greater than or equal to 20 wt % and less than or equal to 40 wt % of low CTE additive component particles.

[0051] Aspect (43) of the present disclosure relates to the decorative article according to aspect (42), wherein each of the plurality of low CTE additive component particles comprises glass, glass frit, glass enamel, ceramic enamel, glass ceramic, or ceramic material.

[0052] Aspect (44) of the present disclosure relates to the decorative article according to any one of aspects (38)-(43), wherein the decorative layer comprises greater than or equal to 5 wt % of a pigment additive.

[0053] Aspect (45) of the present disclosure relates to the decorative article according to aspect (44), wherein the pigment additive includes at least one of a CuCr-based pigment, a MgFe-based pigment, and a FeCrCoNi-based pigment.

[0054] Aspect (46) of the present disclosure relates to the decorative article according to any one of aspects (42)-(45), wherein the low CTE additive component particles and the pigment additive, if present, comprise an average particle size of less than or equal to 10 μm.

[0055] Aspect (47) of the present disclosure relates to a decoration according to any one of aspects (38)-(46), further comprising a second glass substrate and an intermediate layer disposed between the second glass substrate and the second major surface, wherein a polymeric material of the intermediate layer is present in a plurality of pores.

[0056] Aspect (48) of the present disclosure relates to the decorative article according to aspect (47), wherein the glass article exhibits an L* value of less than or equal to 10 in the area where the decorative layer is provided.

[0057] Aspect (49) of the present disclosure relates to a decoration according to any one of aspects (47)-(48), wherein when light from a D65 illumination source is reflected from a glass substrate, the light exhibits a maximum ΔE value calculated using the CIE76 formula and between two different positions of the glass article on which the decorative layer is disposed that is less than or equal to 3.0.

[0058] Aspect (50) of the present disclosure relates to the decorative glass article according to any one of aspects (1)-(17) and (38)-(49), wherein the decorative layer covers greater than or equal to 5% of the total surface area of ​​the second major surface.

[0059] Additional features and advantages will be set forth in the following detailed description, and those skilled in the art may understand the additional features and advantages in part from this description, or may learn the additional features and advantages by practicing the embodiments described herein, including the following detailed description, claims, and drawings.

[0060] It is to be understood that both the foregoing general description and the following detailed description are merely exemplary, and are intended to provide an overview or framework for understanding the nature and character of the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] The accompanying drawings are included to provide a further understanding and are incorporated into and constitute a part of this specification. The accompanying drawings illustrate one or more embodiments and together with the description explain the principles and operation of the various embodiments. In the drawings:

[0062] Figure 1 is an illustration of a vehicle including an automotive glazing according to one or more embodiments of the present disclosure;

[0063] Figure 2 Depicts a method for performing a process according to one or more embodiments of the present disclosure. Figure 1 A cross-sectional view of a car glass window along line segment 2-2;

[0064] Figure 3 depicts a cross-sectional view of a curved laminate including a decorative layer according to one or more embodiments of the present disclosure;

[0065] Figure 4 A flow chart depicting a method of making a decorative glass article and a laminate including a decorative glass article according to one or more embodiments of the present disclosure;

[0066] Figure 5is a graph comprising a Weibull distribution of a plurality of exemplary decorative glass articles according to one or more embodiments of the present disclosure;

[0067] Figure 6 is a graph of surface height measurements for determining the thickness of a decorative layer of an exemplary decorative glass article according to one or more embodiments of the present disclosure;

[0068] Fig. 7A is a scanning electron microscope image of an exemplary decorative glass article including a porous decorative layer according to one or more embodiments of the present disclosure;

[0069] Figure 7B is a scanning electron microscope image of an exemplary decorative glass article including a porous decorative layer according to one or more embodiments of the present disclosure;

[0070] Figure 7C is a scanning electron microscope image of an exemplary decorative glass article including a non-porous decorative layer according to one or more embodiments of the present disclosure;

[0071] Figure 8 is a graph containing a Weibull distribution of a plurality of exemplary decorations according to one or more embodiments of the present disclosure;

[0072] Fig. 9A is a scanning electron microscope image of a non-porous decorative layer disposed on a soda-lime-silicate glass substrate according to one or more embodiments of the present disclosure;

[0073] Fig. 9B is a scanning electron microscope image of a porous decorative layer disposed on a soda-lime-silicate glass substrate according to one or more embodiments of the present disclosure;

[0074] Fig. 9C is a graph of Weibull distributions of a plurality of glass articles having soda-lime silicate glass substrates in accordance with one or more embodiments of the present disclosure;

[0075] Fig. 10A is a scanning electron microscope image of a porous decorative layer disposed on a borosilicate glass substrate according to one or more embodiments of the present disclosure;

[0076] Fig. 10B is a scanning electron microscope image of a porous decorative layer disposed on a borosilicate glass substrate according to one or more embodiments of the present disclosure;

[0077] Fig. 10C is a graph of Weibull distributions of a plurality of glass articles having a borosilicate glass substrate according to one or more embodiments of the present disclosure;

[0078] Fig.11 is a scanning electron microscope image of a porous decorative layer disposed on a borosilicate glass substrate according to one or more embodiments of the present disclosure;

[0079] Fig. 12A are a plurality of scanning electron microscope images of a plurality of glass articles having a decorative layer disposed therein including different amounts of porosity according to one or more embodiments of the present disclosure;

[0080] Fig. 12B According to one or more embodiments of the present disclosure Fig. 12A A graph showing the B5 value of a plurality of glazings as a function of the porosity of the decorative layer;

[0081] Fig.13A is an image of a glass article including a porous decorative layer before lamination with a second glass substrate via a polymer interlayer according to one or more embodiments of the present disclosure;

[0082] Fig. 13B is a glass substrate after being laminated with a second glass substrate via a polymer interlayer according to one or more embodiments of the present disclosure Fig.13A Images of the glasswork shown;

[0083] Fig.14A is an image of a glass article formed of a porous decorative layer including porosity-inducing component particles having a d50 particle size of 1.0 μm according to one or more embodiments of the present disclosure;

[0084] Fig. 14B is an image of a glass article formed of a porous decorative layer including porosity-inducing component particles having a d50 particle size of 2.5 μm according to one or more embodiments of the present disclosure;

[0085] Fig. 14C is an image of a glass article formed of a porous decorative layer including porosity-inducing component particles having a d50 particle size of 5.0 μm according to one or more embodiments of the present disclosure;

[0086] Fig.15A According to one or more embodiments of the present disclosure, FIG. 14A to FIG. 14C Plots of Weibull B5 and ratio values ​​as a function of porosity inducing component particle size for the examples shown;

[0087] Fig. 15B is a graph of Weibull B5 and ratio values ​​as a function of porosity-inducing component particle size for another set of exemplary glass articles according to one or more embodiments of the present disclosure;

[0088] Fig.16is a graph showing integrated optical transmission of samples constructed using a set of exemplary glass articles shown in FIG. 15C before and after lamination according to one or more embodiments of the present disclosure;

[0089] It should be understood that numerous other modifications and examples can be devised by those skilled in the art that fall within the scope and spirit of the principles of this disclosure. DETAILED DESCRIPTION

[0090] Referring generally to the accompanying drawings, a decorative glass article comprising a glass substrate and a decorative layer is described herein. The decorative layer is porous (e.g., a porosity greater than or equal to 5%, greater than or equal to 10%, greater than or equal to 12%, greater than or equal to 14%, greater than or equal to 16%, greater than or equal to 18%, greater than or equal to 20%, greater than or equal to 21%, greater than or equal to 22%, greater than or equal to 23%, greater than or equal to 24%, greater than or equal to 25%, less than or equal to 30%). In an embodiment, the glass substrate may include less than or equal to 55x10 -7 K -1 (For example, less than or equal to 50×10 -7 K -1 , less than or equal to 45×10 -7 K -1 , less than or equal to 40×10 -7 K -1 , less than or equal to 35×10 -7 K -1 , less than or equal to 32.5×10 -7 K -1 ), a first major surface, and a second major surface disposed opposite the first major surface. The decorative layer may be disposed on the second major surface of the glass substrate and cover a suitable portion of the glass substrate. In an embodiment, the area of ​​the surface occupied by the decorative layer is less than 60%, 50%, 40%, 30%, 20%, 10%, 5%, 1%, 0.1%, or less than 0.01% of the total surface area of ​​the second major surface. The CTE of the decorative layer is within 23×10 -7 K -1 The decorative layer is preferably formed on the second major surface of the glass substrate, such that although the decorative layer is in contact with the glass substrate, the decorative layer does not reduce the mechanical strength of the glass substrate. The decorative layer can be deposited on the second major surface of the glass substrate using a suitable pattern for decorative or concealing purposes. The relatively low CTE of the decorative layer described herein enables the use of various borosilicate glasses in automotive glass applications (e.g., in components of automotive glass windows (e.g., side windows, windshields)) compared to certain existing commercially available enamels.

[0091] When deposited on glass (e.g., automotive glass), the decorative layers described herein can act as decorative enamels. Decorative enamels can be used for aesthetic purposes, functional purposes, or both. Typically, decorative glass frits have a dual function: providing an attractive appearance and acting as a barrier to block visible and UV light.

[0092] In one embodiment, the decorative layer is formed by a suitable ceramic enamel and a low CTE additive component. Certain existing commercially available ceramic enamels are generally incompatible with low CTE glasses (e.g., borosilicate glasses) because such enamels have a relatively high CTE compared to such borosilicate glasses. Such CTE differences may result in a decrease in the strength of the glass (making the decorative glass article weaker than the undecorated substrate). Therefore, in an embodiment, the low CTE additive component included in the decorative layer is at least 5 wt % (e.g., at least 10 wt %, at least 12 wt %, at least 14 wt %, at least 16 wt %, at least 18 wt %, at least 20 wt %, at least 22 wt %, at least 24 wt %, at least 26 wt %, at least 28 wt %, at least 30 wt %), such that the CTE (CTE) of the glass substrate is 1.5 wt %. glass ) and the CTE of the decorative layer (CTE d ) is less than or equal to 15×10 - 7 K -1 (For example, less than or equal to 10×10 -7 K -1 , less than or equal to 8×10 -7 K -1 , less than or equal to 8×10 -7 K -1 , less than or equal to 7×10 -7 K -1 , less than or equal to 6×10 -7 K -1 , less than or equal to 5×10 -7 K -1 , less than or equal to 4×10 -7 K -1 , less than or equal to 3×10 -7 K -1 , less than or equal to 2×10 -7 K -1 , less than or equal to 1×10 -7 K -1 , less than or equal to 0.5×10 -7 K -1 , less than or equal to 0.1×10 -7 K -1, or any other range described herein). Such CTE matching can help prevent defects in the decorative layer from forming during manufacture of the glass article and enable the decorative glass article to exhibit favorable mechanical strength properties.

[0093] It has been found that adding a low CTE additive component to a ceramic enamel can result in porosity in the decorative layer after the ceramic enamel is fired. It has been found that the porosity can prevent the decorative layer from reducing the strength of the glass substrate, and in some cases can even increase the strength of the glass substrate. The porosity is introduced during the curing process of the enamel. In an embodiment, for example, a low CTE additive component (e.g., in particulate form) is added to a commercially available ceramic enamel with a suitable medium to obtain a modified enamel that can be applied to a glass substrate via a suitable application technique, and then cured to form a porous structure.

[0094] In aspects, a modified enamel including any of the low CTE additive components described herein can have various properties suitable for automotive glass production. For example, in an embodiment, the modified enamel is compatible with the temperature requirements for bending a decorative glass product in a process of forming a laminate and laminating it with another glass product. In an embodiment, the uncured modified enamel can be cured before or during a heating stage associated with bending a glass substrate into a shape suitable for a glazing application. For example, in an embodiment, the modified enamel can be cured during a heating cycle of a bending process to promote processing efficiency. Therefore, in an embodiment, the glass softening temperature of the modified enamel is less than or equal to the sag temperature of the glass substrate. In an embodiment, the glass softening temperature of the modified enamel can be less than or equal to 750°C (e.g., less than or equal to 725°C, less than or equal to 700°C, less than or equal to 675°C, less than or equal to 650°C, less than or equal to 625°C, less than or equal to 600°C, less than or equal to 575°C, less than or equal to 550°C) to promote this simultaneous bending and curing action.

[0095] After the ceramic enamel is fired on the glass substrate and cooled, the decorative layer may include a thickness of less than or equal to 30 μm (e.g., less than or equal to 25 μm, greater than or equal to 1.0 μm and less than or equal to 25.0 μm, greater than or equal to 5.0 μm and less than or equal to 25.0 μm, greater than or equal to 5.0 μm and less than or equal to 20.0 μm, greater than or equal to 5.0 μm and less than or equal to 10.0 μm). The decorative layer may also include a porous structure due to the incorporation of the low CTE additive component. It has been found that the porosity can prevent the decorative layer from reducing the mechanical strength of the glass substrate. Without wishing to be bound by theory, it is believed that the porosity reduces the size of the area of ​​continuous contact between the glass substrate and the decorative enamel, thereby reducing the CTE-induced stress accumulation caused during the manufacture of the decorative glass article, thereby preventing defect formation and propagation. In embodiments, the porosity of the decorative layer described herein ranges from 5% to 40% (e.g., 15% to 40%, 20% to 40%, 20% to 30%, 25% to 30%). Porosity can also help give the decorative layer a desired color appearance when incorporated into a laminate. For example, in embodiments, an interlayer used to attach a decorative glass substrate to another glass substrate can at least partially fill some of the pores in the decorative layer, which can darken the appearance of the decorative enamel.

[0096] The decorative enamel may also include optical properties that are beneficial for decorative automotive applications. For example, in embodiments, at a thickness of less than or equal to 30 μm as described herein, the decorative layer may exhibit a relatively high blackness (e.g., an L* value of less than or equal to 20, less than or equal to 15, less than or equal to 5, less than or equal to 2.5 according to the CIELAB color coordinate system). In embodiments, the decorative layer exhibits an integrated visible light transmittance of less than or equal to 2.0% (e.g., less than or equal to 1.8%, less than or equal to 1.6%, less than or equal to 1.4%, less than or equal to 1.2%, less than or equal to 1.0%, less than or equal to 0.8%, less than or equal to 0.6%, less than or equal to 0.4%, less than or equal to 0.2%, less than or equal to 0.1%) for light from 400 nm to 700 nm incident normally on the glass article. This low optical transmittance helps the decorative layer perform various concealing and decorative functions in automotive applications.

[0097] As used herein, the terms "optical transmission," "percent transmission," and "transmittance" are used interchangeably and refer to the percentage of light transmitted through an article within a wavelength range of interest. The "integrated visible light transmittance" for light within a particular wavelength range is determined using the following formula:

[0098]

[0099] where T(λ) represents the transmittance spectrum over a range of wavelengths, and φ(λ) is equal to the transmission of the light source used to measure the transmission.

[0100] As used herein, unless otherwise specified herein, the term "coefficient of thermal expansion" or CTE refers to a value obtained by measuring the expansion of a referenced material between temperatures of 25°C and 300°C.

[0101] Embodiments of the decorative glass articles are described herein with reference to Figure 1 The vehicle 100 shown in the drawings is described. The vehicle 100 includes a body 110 defining an interior and at least one opening 120 communicating with the interior. The vehicle 100 further includes an automotive glass window 130 (i.e., a window) disposed in the opening 120. The automotive glass window 130 includes at least one interlayer having one of the decorative glass products described herein. The automotive glass window 130 may form at least one of a sidelight, a windshield, a rear window, a window, and a sunroof in the vehicle 100. In some embodiments, the automotive glass window 130 may form an interior partition (not shown) in the interior of the vehicle, or may be disposed on an exterior surface of the vehicle 100 and form an engine body cover, a headlight cover, a taillight cover, a door panel cover, or a pillar cover. The vehicle 100 used herein includes an automobile ( Figure 1 Examples of the invention include rail vehicles, locomotives, boats, ships, and airplanes, helicopters, drones, spacecraft, and the like. In addition, although the present disclosure is framed in a vehicle, the decorative glass articles described herein can be used in other environments (e.g., architectural glass windows or bulletproof glass window applications).

[0102] Figure 2 Schematically depicts a diagram of a process according to one or more embodiments of the present disclosure. Figure 12-2 of the automotive glass window 130. As shown, the automotive glass window 130 includes a first glass interlayer 200, a second glass interlayer 220, and an intermediate layer 230 disposed between the first glass interlayer 200 and the second glass interlayer 220. As used herein, the term "glass interlayer" can be used interchangeably with the term "glass substrate". The first glass interlayer 200 includes a first major surface 202, a second major surface 204, and a thickness 206 extending between the first major surface 202 and the second major surface 204. The second glass interlayer 220 includes a first major surface 222, a second major surface 224, and a thickness 226 extending between the first major surface 222 and the second major surface 224. The intermediate layer 230 includes a thickness 236 and is used to bond the first major surface 222 to the second major surface 204. In an embodiment, the first major surface 202 of the first glass interlayer 200 forms the outer surface of the automotive glazing 130 (and faces the exterior of the vehicle 100 ), while the second major surface 224 of the second glass interlayer 220 forms the inner surface of the automotive glazing 130 (and faces the interior of the vehicle 100 ).

[0103] In an embodiment, the first glass interlayer 200 includes, consists of, or consists essentially of a borosilicate glass composition. Therefore, the first thermal expansion coefficient included in the first glass interlayer 200 may be less than or equal to 55×10 -7 K -1 (For example, less than or equal to 52.5×10 -7 K -1 , less than or equal to 50×10 -7 K -1 , less than or equal to 47.5×10 -7 K -1 , less than or equal to 45×10 -7 K -1 , less than or equal to 42.5×10 -7 K -1 , less than or equal to 40×10 -7 K -1 , less than or equal to 37.5×10 -7 K -1 , less than or equal to 35×10 -7 K -1 , less than or equal to 32.5×10 -7 K -1 , less than or equal to 32×10 -7 K -1 ). Such a CTE range may make the first glass interlayer 200 incompatible with decoration via existing commercially available enamels.

[0104] In an embodiment, the first glass interlayer 200 includes a borosilicate glass composition, the borosilicate glass composition includes 60 mol% to 90 mol% SiO2, about 1 mol% to about 20 mol% Al2O3, 7 mol% to 16 mol% B2O3, 2 mol% to 20 mol% R2O, wherein R2O includes a combined amount of Na2O, Li2O, and K2O. For example, in an embodiment, the borosilicate glass composition includes about 83.60 mol% SiO2, about 1.20 mol% Al2O3, about 11.60 mol% B2O3, about 3.00 mol% Na2O, and about 0.70 mol% K2O, and includes about 32×10 -7 K -1 When the first glass interlayer 200 constitutes the outer interlayer of the automotive glazing 130 (e.g., such that the first major surface 202 is the outer surface of the automotive glazing 130), such borosilicate glass may be particularly beneficial because it may have greater thermal shock resistance and be more resistant to cracking from impact events from road debris (e.g., rocks or the like) than soda-lime silicate glass currently used as the outer interlayer in automotive glazings. Borosilicate glass is known to exhibit unusual fracture behavior and is less susceptible to cracking that propagates radially from the point of debris impact, which is particularly beneficial for the durability of automotive glazings.

[0105] In an embodiment, the first glass interlayer 200 particularly advantageously includes U.S. Provisional Patent Application 63 / 123863, entitled “Fusion Formable Borosilicate Glass Composition and Articles Formed Therefrom” filed on December 10, 2020, U.S. Provisional Patent Application 63 / 183271, entitled “Fusion Formable Borosilicate Glass Composition and Articles Formed Therefrom” filed on May 3, 2021, U.S. Provisional Patent Application 63 / 183292, entitled “Glass with Unique Fracture Behavior for Vehicle Windshield” filed on May 3, 2021, U.S. Patent Application 17 / 363266, entitled “Glass with Unique Fracture Behavior for Vehicle Windshield” filed on June 30, 2021, and U.S. Patent Application 17 / 363267, entitled “Glass with Unique Fracture Behavior for Vehicle Windshield” filed on December 6, 2021. One of the fusible borosilicate glass compositions described in International Patent Application PCT / US2021 / 061966 entitled "Windshield", the contents of each of which are incorporated herein by reference in their entirety. In an embodiment, such a borosilicate glass composition includes (in terms of constituent oxides) SiO2, B2O3, Al2O3, one or more alkali metal oxides, and one or more divalent cation oxides selected from the group consisting of MgO, CaO, SrO, BaO, and ZnO. In an embodiment, the borosilicate glass composition includes, for example, greater than or equal to 11 mol% and less than or equal to 16 mol% of B2O3, greater than or equal to 2 mol% and less than or equal to 6 mol% of Al2O3, and greater than or equal to 7.0 mol% of the total amount of Na2O, KO, MgO, and CaO. The concentrations of SiO2, B2O3, one or more alkali metal oxides, Al2O3, and one or more alkaline earth metal oxides, based on the mole percentage of the oxides, satisfy the following relationship: (R2O+R'O)≧Al and 0.80<(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])<0.93, where R2O is the concentration of one or more alkali metal oxides and R'O is the sum of the concentrations of one or more alkaline earth metal oxides. It has been found that such glasses exhibit favorable ring fracture behavior to prevent defects from radially propagating from the impact point.

[0106] In an embodiment, the first glass interlayer 200 includes a fusion-formable borosilicate glass composition, the borosilicate glass composition including 74 mol% to 80 mol% SiO2, 2.5 mol% to 6 mol% Al2O3, 11.5 mol% to 14.5 mol% B2O3, 4.5 mol% to 8 mol% Na2O, 0.5 mol% to 3 mol% K2O, 0.5 mol% to 2.5 mol% MgO, and 0 mol% to 4 mol% CaO (e.g., such that the combined amount of CaO and MgO is less than 5 mol%), and includes greater than or equal to 32.5×10 -7 K -1 and less than or equal to 56×10 -7 K -1 (For example, greater than or equal to 40×10 -7 K -1 and less than or equal to 50×10 -7 K -1 , greater than or equal to 42×10 -7 K -1 and less than or equal to 48×10 -7 K -1 , greater than or equal to 43×10 -7 K -1 and less than or equal to 47×10 -7 K -1). The fusible glass composition may include SiO2, B2O3, one or more alkali metal oxides (R2O), Al2O3, and one or more divalent cation oxides R'O in concentrations based on the molar percentage of the oxides such that the concentrations satisfy some (e.g., one or more combinations of) or all of the following relationships: (Relationship 1) SiO2≧72 mol % (e.g., SiO2≧72.0, e.g., SiO2≧73.0, e.g., SiO2≧74.0, and / or SiO2≦92, e.g., SiO2≦90); (Relationship 2) B2O3≧10 mol % (e.g., B2O3≧10.0, e.g., B2O3≧10.5, and / or B2O3≦20, for example B2O3≦18); (Relationship 3) (R2O+R'O)≧Al2O3, for example (R2O+R'O)≧(Al2O3+1), for example (R2O+R'O)≧(Al2O3+2); and / or (Relationship 4) 0.80≦(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])≦0.93, wherein R2O is the sum of the concentrations of one or more alkali metal oxides, and when included in the borosilicate glass composition, R'O is the sum of the concentrations of one or more divalent cation oxides. R2O may be, for example, the sum of Li2O, Na2O, K2O, Rb2O, Cs2O, and R'O may be, for example, the sum of MgO, CaO, SrO, BaO, ZnO. Compositions satisfying equations 1-4 described in this paragraph may tend to exhibit unique fracture behavior of forming annular cracks around the area of ​​contact between the glass and the striker and preventing radial crack propagation. Such fused glasses may also exhibit excellent chemical durability, scratch resistance, mechanical strength, and optical properties (e.g., from the perspective of optical transmission and optical distortion) compared to other borosilicate glasses. Examples of such glass compositions are provided herein.

[0107] Still reference Figure 2In an embodiment, the second glass interlayer 220 includes, consists of, or consists essentially of a second glass composition, the second glass composition being different from the glass composition used to form the first glass interlayer 210. In an embodiment, the second glass composition includes a soda-lime silicate composition, an aluminosilicate glass composition, an alkali aluminosilicate glass composition, an alkali-containing borosilicate glass composition, an alkali aluminophosphosilicate glass composition, or an alkali aluminoborosilicate glass composition. In an embodiment, the second glass interlayer 220 includes one of the boroaluminosilicate glass compositions described in U.S. Provisional Patent Application No. 63 / 318,221, filed on March 9, 2022, entitled “Boroaluminosilicate Glass Composition having High Fusion Flow Rate and Advantaged Pair Shaping Temperature”. In an embodiment, the second glass interlayer 220 is formed of one of the glass compositions described in U.S. Patent Application 16 / 002276, entitled “Automotive Glass Compositions, Articles, and Hybrid Laminates” filed on June 7, 2018, or U.S. Patent 10,125,044, entitled “Ion Exchangeable High Damage Resistance Glasses” filed on November 14, 2014. The contents of each of these patent applications are incorporated herein by reference in their entirety.

[0108] Regardless of the specific compositions used to form the first glass interlayer 200 and the second glass interlayer 220, embodiments are contemplated in which both the first glass interlayer 200 and the second glass interlayer 220 are not strengthened (e.g., chemically strengthened, thermally strengthened, or mechanically strengthened). Embodiments are also contemplated in which at least one of the first glass interlayer 200 and the second glass interlayer is strengthened (e.g., chemically, thermally, or mechanically). In embodiments, for example, the second glass interlayer 220 is chemically strengthened (e.g., when composed of a suitable alkali-aluminosilicate glass composition), while the first glass interlayer 200 is unstrengthened (but may be optionally annealed) and exhibits a surface compressive stress of less than about 3 MPa, or about 2.5 MPa or less, 2 MPa or less, 1.5 MPa or less, 1 MPa or less, or about 0.5 MPa or less. Such embodiments can help reduce the weight of automotive glazing while still providing advantageous mechanical strength and meeting various regulatory requirements associated with automotive applications. Embodiments are also contemplated where both the first glass interlayer 200 and the second glass interlayer 220 are strengthened.

[0109] The thickness of the components of the automotive glazing 130 will now be described. In an embodiment, the first thickness 206 is at least 0.5 mm, at least 1 mm, at least 2 mm, at least 3 mm, at least 3.3 mm, or at least 3.8 mm. In one or more embodiments, the first thickness ranges from about 0.1 mm to about 6 mm, 0.2 mm to about 6 mm, 0.3 mm to about 6 mm, 0.4 mm to about 6 mm, 0.5 mm to about 6 mm, 0.6 mm to about 6 mm, 0.7 mm to about 6 mm, 0.8 mm to about 6 mm, 0.9 mm to about 6 mm, 1 mm to about 6 mm, 1.1 mm to about 6 mm, 1.2 mm to about 6 mm, 1.3 mm to about 6 mm, 1.4 mm to about 6 mm, 1.5 mm to about 6 mm, 1.6 mm to about 6 mm, about 1.8 mm to about 6 mm, about 2 mm to about 6 mm, about 2.2 mm to about 6 mm, about 2.4mm to about 6mm, about 2.6mm to about 6mm, about 2.8mm to about 6mm, about 3mm to about 6mm, about 3.1mm to about 6mm, about 3.2mm to about 6mm, about 3.3mm to about 6mm, about 3.4mm to about 6mm, about 3.5mm to about 6mm, about 3.6mm to about 6mm, about 3.7mm to about 6mm, about 3.8mm to about 6mm, about 3.9mm to about 6mm, about 4mm to about 6mm, about 4.2mm to about 6mm, about 4.4mm to about 6mm, about 4.5mm to about 6mm, about 4.6mm to about 6mm, about 4.8mm to about 6mm, about 5mm to about 6mm, about 5.2mm to about 6mm, about 5.4mm to about 6mm, about 5.5mm to about 6mm, about 5.6mm to about 6mm, about 5.8mm to about 6mm, about 1.6mm to about 5.8mm, about 1.6mm to about 5.6mm, about 1.6mm to about 5.5mm, about 1.6mm to about 5.4mm, about 1.6mm to about 5.2mm, about 1.6mm to about 5mm, about 1.6mm to about 4.8mm, about 1.6mm to about 4.6mm, about 1.6mm to about 4.4mm, about 1.6mm to about 4.2mm, about 1.6mm to about 4.9mm, about 1.6mm to about 3.9mm. m, about 1.6 mm to about 3.8 mm, about 1.6 mm to about 3.7 mm, about 1.6 mm to about 3.6 mm, about 1.6 mm to about 3.5 mm, about 1.6 mm to about 3.4 mm, about 1.6 mm to about 3.3 mm, about 1.6 mm to about 3.2 mm, about 1.6 mm to about 3.1 mm, about 1.6 mm to about 3 mm, about 1.6 mm to about 2.8 mm, about 1.6 mm to about 2.6 mm, about 1.6 mm to about 2.4 mm, about 1.6 mm to about 2.2 mm, about 1.6 mm to about 2 mm, about 1.6 mm to about 1.8 mm, about 3 mm to about 5 mm, or about 3 mm to about 4 mm.

[0110] In an embodiment, the thickness 226 of the second glass interlayer 220 is less than the thickness 206. In an embodiment, the thickness is less than or equal to 2.0 mm (e.g., greater than or equal to 0.1 mm and less than or equal to 2.0 mm, greater than or equal to 0.1 mm and less than or equal to 1.8 mm, greater than or equal to 0.1 mm and less than or equal to 1.6 mm, greater than or equal to 0.5 mm and less than or equal to 1.5 mm, greater than or equal to 0.7 mm and less than or equal to 1.4 mm, greater than or equal to 0.7 mm and less than or equal to 1.2 mm, greater than or equal to 0.7 mm and less than or equal to 1.1 mm). In an embodiment, the total glass thickness (i.e., thickness 206 plus thickness 226) is 8 mm or less, 7 mm or less, 6.5 mm or less, 6 mm or less, 5.5 mm or less, or 5 mm or less. In an embodiment, the lower limit of the total glass thickness is about 2 mm.

[0111] The interlayer 230 bonds the second major surface 204 of the first glass interlayer 200 to the first major surface 222 of the second glass interlayer 220. In an embodiment, the interlayer 230 includes a polymer (e.g., at least one of polyvinyl butyral (PVB), soundproofing PVB (APVB), ionomer, vinyl acetate (EVA), thermoplastic polyurethane (TPU), polyester (PE), polyethylene glycol terephthalate (PET), and the like). The thickness 236 of the interlayer 230 can range from about 0.5 mm to about 2.5 mm (more particularly, about 0.7 mm to about 1.5 mm). In other embodiments, the thickness 236 can be less than 0.5 mm or more than 2.5 mm. In addition, in an embodiment, the interlayer 330 can include multiple polymer layers or films to provide various functions. For example, in an embodiment, the interlayer 230 can be combined with at least one of display, solar insulation, sound insulation, antenna, anti-glare processing, or anti-reflection processing, etc. In certain embodiments, the intermediate layer 230 is modified to provide ultraviolet (UV) absorption, infrared (IR) absorption, IR reflection, acoustic control / damping, adhesion promotion, and coloring. The intermediate layer 230 can be modified by suitable additives (e.g., dyes, pigments, dopants, etc.) to impart desired properties.

[0112] In an embodiment, in addition to the interlayer 230, at least one of the first glass interlayer 200 and the second glass interlayer 220 is provided with a functional coating or a decorative coating. Such a functional coating or a decorative coating may be deposited on any of the first major surface 202, the second major surface 204, the first major surface 222, and the second major surface 224. In an embodiment, the coating is at least one of an infrared reflective (IRR) coating, a glass frit, an anti-reflective coating, or a pigment coating. In an exemplary embodiment of IRR, the second major surface 204 of the first glass interlayer 310 or the first major surface 222 of the second glass interlayer 220 is coated with an infrared reflective film (and optionally one or more layers of transparent dielectric film). In an embodiment, the infrared reflective film includes a conductive metal (e.g., silver, gold, or copper) that reduces the transmission of heat through the automotive glass window. In an embodiment, the optional dielectric film may be used to anti-reflect against the infrared reflective film and control other properties and characteristics of the coating (e.g., color and durability). In an embodiment, the dielectric film includes one or more oxides of zinc, tin, indium, bismuth, and titanium, etc. In an exemplary embodiment, the IRR coating includes one or two silver layers, each sandwiched between two transparent dielectric films. In an embodiment, the IRR coating is applied using, for example, physical or chemical vapor deposition or via lamination.

[0113] In an embodiment, at least one of the first glass interlayer 200 and the second glass interlayer 220 includes a decorative layer disposed thereon. In the illustrated embodiment, for example, the first decorative layer 240 is disposed on the first major surface 222 of the second glass interlayer 220, and the second decorative layer 250 is disposed on the second major surface 204 of the first glass interlayer 200. Such decorative layers can be used to protect the adhesive used to attach the automotive glass window 130 to the opening 120 from degradation due to exposure to UV light. Providing the first decorative layer 240 and the second decorative layer 250 on the inner surface of the laminate is beneficial because it can be used, for example, to protect the IRR coating from mechanical degradation and / or oxidation. In addition, placing the first decorative layer 240 and the second decorative layer 250 on the second major surface 204 and the first major surface 222 can also help hide any IRR film or other components (e.g., conductive components associated with a defogging system) embedded between the first glass interlayer 200 and the second glass interlayer 220. Multiple decorative bands are particularly useful for providing a desired aesthetic appearance when the first glass interlayer 200 and the second glass interlayer 220 are comprised of glass having different compositions and / or thicknesses.

[0114] As described herein, embodiments are contemplated in which the first glass interlayer 200 and the second glass interlayer 220 are formed of different compositions. For example, in an embodiment, the first glass interlayer 200 is formed of less than or equal to 55×10 -7 K -1 (For example, less than or equal to 52.5×10-7 K -1 , less than or equal to 50×10 -7 K -1 , less than or equal to 47.5×10 -7 K -1 , less than or equal to 45×10 -7 K -1 , less than or equal to 42.5×10 -7 K -1 , less than or equal to 40×10 -7 K -1 , less than or equal to 37.5×10 -7 K -1 , less than or equal to 35×10 -7 K -1 , less than or equal to 32.5×10 -7 K -1 , less than or equal to 32×10 -7 K -1 ) of a borosilicate glass composition. In this embodiment, the second glass interlayer 220 may be made of soda-lime silicate glass or a glass having a CTE greater than that of the borosilicate glass composition (e.g., greater than or equal to 60×10 -7 K -1 , greater than or equal to 60×10 -7 K -1 and less than or equal to 120×10 -7 K -1 , greater than or equal to 70×10 -7 K -1 and less than or equal to 120×10 -7 K -1 , greater than or equal to 80×10 -7 K -1 and less than or equal to 120×10 -7 K -1 ) is formed of a chemically strengthenable alkali-aluminosilicate glass composition having a CTE of at least 5×10 -7 K -1 (For example, at least 5×10 -7 K -1 , at least 10×10 -7 K -1 , at least 20×10 -7 K -1 , at least 25×10 -7 K -1 , at least 30×10 -7 K -1 , at least 35×10 -7 K-1 , at least 40×10 -7 K -1 , at least 40×10 -7 K -1 , at least 45×10 -7 K -1 , at least 50×10 -7 K -1 ). For example, consider an example in which the first glass interlayer 200 is composed of a glass having a thickness of approximately 32×10 -7 K -1 The second glass interlayer 220 is composed of a glass having a first CTE of about 90×10 -7 K -1 Assume another example where the first glass interlayer 200 is composed of glass having a second CTE of approximately 45×10 -7 K -1 The second glass interlayer 220 is composed of a glass having a first CTE of about 90×10 -7 K -1 The second CTE of the glass composition.

[0115] In the embodiment, preferably, the first decoration layer 240 and the second decoration layer 250 are made of a laminated glass sandwich having a thickness of 10×10 -7 K -1 That is, preferably, the first CTE of the first decorative layer 240 is 10×10 of the CTE of the second glass interlayer 220. -7 K -1 The second CTE of the second decorative layer 250 is 10×10 of the CTE of the first glass interlayer 200. -7 K -1 As described herein, given that the first glass interlayer 200 and the second glass interlayer 220 may be formed of glasses having significantly different CTEs, the first decorative layer 240 and the second decorative layer 250 may be composed of different materials.

[0116] In an embodiment, the first decorative layer 240 is formed by commercially available ceramic enamel or glass frit. In an embodiment, the first decorative layer 240 is formed by a glass frit designed to be ion-exchangeable. That is, the glass frit can be applied to the ion-exchangeable glass before the ion exchange process. This glass frit is configured to allow the exchange of ions between the glass and the processing bath. In an embodiment, the glass frit is a Bi-Si-B alkali system, a Bi system based on Zn, a Bi-Zn system, a Bi system, a Si-Zn-B-Ti system without Bi or low Bi, a Si-Bi-Zn-B-alkali system, and / or a Si-Bi-Ti-B-Zn-alkali system, etc. An example of an ion-exchangeable glass frit including a colorant includes 45.11 mol % Bi2O3, 20.61 mol % SiO2, 13.56 mol % Cr2O3, 5.11 mol % CuO, 3.48 mol % MnO, 3.07 mol % ZnO, 2.35 mol % B2O3, 1.68 mol % TiO2, 1.60 mol % Na2O, 1.50 mol % Li2O, 0.91 mol% K2O, 0.51mol% Al2O3, 0.15mol% P2O5, 0.079mol% SO3, 0.076mol% BaO, 0.062mol% ZrO2, 0.060mol% Fe2O3, 0.044mol% MoO3, 0.048mol% CaO, 0018mol% Nb2O5, 0.006mol% Cl, and 0.012mol% SrO. Other examples of ion-exchangeable glass frits are disclosed in international patent application PCT / US2020 / 28176, entitled “Filled Pore Decorative Layer for Ion Exchangeable and Automotive Glass,” filed on April 15, 2022, U.S. Patent No. 9,346,708B2 (application No. 13 / 464,493, filed on May 4, 2012), and U.S. Publication No. 2016 / 0002104A1 (application No. 14 / 768,832, filed on August 19, 2015), each of which is incorporated herein by reference in its entirety.

[0117] In an embodiment, the first decorative layer 240 may include (e.g., as an alternative or in addition to the enamel / glass frit-based components described in the previous paragraph) a colorant coating consisting of an ink (e.g., an organic ink). In embodiments particularly suitable for such a colorant coating, the colorant coating may be applied to the first major surface 222 or the second major surface 224. Advantageously, such a colorant coating may be applied to the second glass interlayer 220 while the second glass interlayer 220 is in a planar configuration, and then the second glass interlayer 320 may be cold formed into a curved configuration without destroying the colorant coating (e.g., an organic ink coating). In an embodiment, the colorant coating includes at least one pigment, at least one mineral filler, and an adhesive including an alkoxysilane functionalized isocyanurate or an alkoxysilane functionalized biuret. Examples of such a colorant coating are described in European Patent No. 2617690B1, which is incorporated herein by reference in its entirety. Other suitable colorant coatings and methods of applying colorant coatings are described in U.S. Publication No. 2020 / 0171800A1 (application No. 16 / 613,010, filed on November 12, 2019) and U.S. Patent No. 9,724,727 (application No. 14 / 618,398, filed on February 10, 2015), both of which are incorporated herein by reference in their entirety.

[0118] Still reference Figure 2 Given the relatively low CTE of the first glass interlayer 200, some existing commercially available enamels are not suitable for deposition and curing thereon as the second decorative layer 250. It has been found that some existing decorative enamels have a CTE of approximately 80×10 -7 K -1 The CTE of the first glass interlayer 200 is substantially different from that of the first glass interlayer 200 according to some embodiments described herein. Applicants have found that when deposited and cured on the borosilicate glass described herein, such conventional decorative porcelain enamels exhibit cracks due to CTE mismatch, which reduces the appearance and mechanical strength of the automotive glass window 130.

[0119] Therefore, the second decorative layer 250 is composed of enamel modified by adding one or more low CTE additive components. Due to the addition of one or more low CTE additive components, the CTE (CTE d ) can be in the CTE (GTE) of the first glass interlayer 200 g ) of 10×10 -7 K -1 In the embodiment, 0≦│CTE g –CTE d │≦10, 0≦│CTE g –CTE d │≦9, 0≦│CTE g–CTE d │≤8, 0≤│CTE g –CTE d │≤7, 0≤│CTE g –CTE d │≤6, 0≤│CTE g –CTE d │≤5, 0≤│CTE g –CTE d │≤4, 0≤│CTE g –CTE d │≤3, 0≤│CTE g –CTE d │≤2, 0≤│CTE g –CTE d │≤1, 0≤│CTE g –CTE d │≤0.5, 0≤│CTE g –CTE d │≤0.25, 0≤│CTE g –CTE d │≤0.20, 0≤│CTE g –CTE d │≤0.15, 0≤│CTE g –CTE d │≤0.1, 0≤│CTE g –CTE d │≤.05. In the embodiment, CTE d ≤55×10 -7 K -1 (e.g., 20×10 -7 K -1 ≤CTE d ≤55×10 -7 K -1 、20×10 -7 K -1 ≤CTE d ≤50×10 -7 K -1 、20×10 -7 K -1 ≤CTE d ≤45×10 -7 K -1 、20×10 -7 K -1 ≤CTE d ≤40×10 -7 K -1 、20×10 -7 K -1 ≤CTE d≦35×10 -7 K -1 , 20×10 -7 K -1 ≦CTE d ≦32.5×10 -7 K -1 ,35×10 -7 K -1 ≦CTE d ≦50×10 -7 K -1 , 40×10 -7 K -1 ≦CTE d ≦50×10 -7 K -1 , and any intermediate ranges). As described herein, Applicants have discovered that configuring the second decorative layer 250 to have a CTE close to that of the first glass interlayer 200 can prevent cracks from forming in the second decorative layer 250 during the manufacture of the automotive glazing 130, and can also prevent the incorporation of the second decorative layer 250 from reducing the mechanical strength of the first glass interlayer 200.

[0120] In an embodiment, the second decorative layer 250 is formed by modifying a commercially available enamel by incorporating any one of the low CTE additive components described herein. In an embodiment, the commercially available enamel comprises a glass or ceramic enamel, which comprises a glass frit component, a colorant component, and an optional additive component. The glass frit component determines various properties of the second decorative layer 250 including mechanical strength and required firing conditions. In an embodiment, the glass frit comprises one or more Bi, B, Zn, or Si oxides. The glass frit is characterized in that Bi, B, Zn, or Si oxides are present as main components. In some embodiments, the glass frit has 1 wt%, 5 wt%, or 10 wt% or more of Bi, B, Zn, or Si oxides. In some embodiments, the glass frit has less than 1 mol% of Na2O, less than 10 mol% of Fe2O3, or less than 25 mol% of P2O5. In some embodiments, the glass frit does not contain Na2O, Fe2O3, or P2O5. In an embodiment, the colorant component is incorporated into the glass frit and includes one or more Cu, Co, Fe, Ni, Mn, or Cr oxides. In some embodiments, the colorant includes non-Fe oxides, or does not contain Fe oxides. Examples of suitable ceramic enamels can be obtained from Ferro Corporation (Mayfield Heights, Ohio), including product number 14 316 (a bismuth-based frit system with a black, matte color, 6 minutes under a wide firing range of 570-640°C, and a relatively high melting point) and product number VPS4100 (a black enamel that can be fired at 630-650°C). The enamel can be black, white, or any color (e.g., red, indigo, blue, green, brown, orange, purple, yellow). Commercially available enamels can be dispersed in a suitable medium to form a paste applied to the first glass interlayer 200. In an embodiment, the medium is composed of an oil or organic resin suitable for drying by evaporation of a solvent.

[0121] In an embodiment, the low CTE additive component is added to a commercially available enamel as separate particles of a suitable low CTE material. The addition of the low CTE additive component is not only used to reduce the CTE of the enamel, but also used to increase the porosity of the resulting second decorative layer 250 after curing. In an embodiment, the second decorative layer 250 includes 15 wt % to 50 wt % of the low CTE additive component after curing (e.g., 15 wt % to 45 wt %, 20 wt % to 45 wt %, 20 wt % to 40 wt %, 25 wt % to 45 wt %, 25 wt % to 40 wt %), so that the second decorative layer 250 includes 40 wt % to about 85 wt % of the enamel (e.g., 50 wt % to 85 wt %, 50 wt % to 80 wt %, 50 wt % to 75 wt %, 50 wt % to 70 wt %). The enamel may be approximately 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or 85% by weight of the second decorative layer 250 .

[0122] Before curing, the second decorative layer 250 may include a mixture of ceramic enamel and low CTE additive component particles. In an embodiment, the low CTE additive component particles include an average particle size of less than or equal to 100 μm (e.g., less than or equal to 50 μm, less than or equal to 40 μm, less than or equal to 30 μm, less than or equal to 20 μm). It has been found that the size of the additive particles affects the porosity of the second decorative layer 250 after curing. The low CTE additive component particles can prevent the densification of the surrounding enamel during sintering, and form a porous structure.

[0123] In an embodiment, the low CTE additive component is present as filler particles in the second decorative layer 250. The melting point or softening temperature of the material forming the low CTE additive component may be greater than the melting point or softening temperature associated with the glass frit component in the enamel.

[0124] A variety of suitable materials for the low CTE additive component particles are contemplated within the scope of the present disclosure. In an embodiment, the low CTE additive component comprises a CTE less than or equal to 10×10 -7 K -1 (For example, less than or equal to 5×10 -7 K -1 , less than or equal to 0×10 -7 K -1 , less than or equal to -5×10 -7 K -1 , less than or equal to -10×10 -7 K -1 , less than or equal to -50×10 -7 K -1, less than or equal to -100×10 -7 K -1 ). It has been found that the CTE of the second decorative layer 250 after curing is approximately the weighted average of all constituent components. Therefore, the CTE of the specific CTE additive component (or combination of components) selected determines the weight percentage required to achieve the desired CTE. In an embodiment, the refractive index of the low CTE additive component is greater than or equal to 1.5 and less than or equal to 1.6. In an embodiment, the refractive index of the low CTE additive component is greater than 1.6. A higher refractive index is preferred to maintain a higher opacity of the decorative layer.

[0125] In an embodiment, the low CTE additive component comprises a ceramic or glass ceramic material having a CTE within any of the ranges described herein. An example of a ceramic is made of The developed - 7 K -1 Another exemplary ceramic is a B-eucryptite ceramic having a CTE of less than -10×10 -7 K -1 Aluminum titanate ceramics with a CTE of about 0×10 -7 K -1 CTE Ceramics. In an embodiment, the low CTE additive component includes a negative CTE. Such negative CTE materials may include Bi-Ni-Fe-oxide, Zr-W-oxide, and other suitable materials.

[0126] In addition to CTE, a low CTE additive component can be selected so that the resulting second decorative layer 250 has a desired opacity. For example, a low CTE additive component can be selected to absorb light in the visible spectrum (on average) (e.g., at least 50% of the light, at least 60% of the light, at least 70% of the light, at least 80% of the light, at least 90% of the light). In an embodiment, a low CTE additive component is selected so that when illuminated by a D65 illumination source at a 0° illumination angle, the second decorative layer 250 exhibits a high blackness (e.g., an L* value of less than or equal to 20, less than or equal to 18, less than or equal to 16, less than or equal to 14, less than or equal to 13, less than or equal to 12, less than or equal to 10, less than or equal to 8, less than or equal to 6, less than or equal to 5). The L* values ​​described herein assume a 2° standard observer.

[0127] In an embodiment, the enamel can exhibit a darkness outside of this range when modified only by adding a low CTE additive component alone. For example, the 118 VTC ceramic described above tends to exhibit white and low refractive index. In this case, particles of a suitable pigment can be further added to the enamel to provide the desired appearance. In an embodiment, the amount of pigment particles added is less than or equal to the amount of the low CTE additive component. The pigment can also be incorporated into the base ceramic enamel (e.g., as a colorant component). In an embodiment, the pigment (if included) is added so that when cured, the amount of the pigment present is greater than or equal to 0% by weight and less than or equal to 50% by weight of the second decorative layer 250 (e.g., greater than or equal to 0% by weight and less than or equal to 40% by weight, greater than or equal to 0% by weight and less than or equal to 30% by weight, greater than or equal to 5% by weight and less than or equal to 30% by weight, greater than or equal to 5% by weight and less than or equal to 20% by weight). Examples of suitable pigments include B1G pigment, 30C965 (CuCr-based pigment), and 20F944 (MgFe-based pigment) from Shepherd (Cincinnati, Ohio) and V7709 (CuCr-based pigment) and 240137 (FeCrCoNi-based pigment) from Ferro Corporation (Mayfield Heights, Ohio). The pigment may be black, blue, green, brown, orange, violet, yellow, or metallic variations thereof. In various embodiments, the pigment and the enamel have the same or similar color (e.g., when illuminated with a D65 illuminator at a 0° illumination angle, the pigment and the enamel may exhibit a* and b* values ​​that differ from each other by less than 5).

[0128] In an embodiment, pigments having the following main components are selected to obtain the desired color, such as the following: black (CuCrFe, CrFe, manganese ferrite spinel, FeCrCoNi), blue (cobalt aluminate, cobalt chromite spinel, CoZnCrAl), green (cobalt titanium green spinel), brown (manganese antimony titanium rutile, zinc iron chromium iron brown spinel, iron titanium brown spinel), orange (rutile tin zinc), purple (cobalt phosphate), yellow (nickel antimony titanium rutile, niobium sulfur tin zinc oxide), and metallic aspects (titanate-covered mica flakes, titanate and tin oxide, or iron oxide).

[0129] Applicants have discovered that incorporating a low CTE additive component and pigment (if included) into the enamel introduces a certain level of porosity into the second decorative layer 250 after curing. The level of porosity is affected by the glass frit composition, particle size, the amount of low CTE additive component and pigment added, and the firing temperature. Without wishing to be bound by theory, it is believed that greater amounts of low CTE additive component or lower firing temperatures will result in increased porosity. As described herein, it has been discovered that at least some porosity in the second decorative layer 250 helps increase the mechanical strength of the automotive glazing 130, particularly when the CTE of the second decorative layer 250 differs from the CTE of the first glass interlayer 200 by at least 5×10 -7 K -1 (For example, when 5≦│CTE g –CTE d │≦10). It is believed that porosity beneficially helps to reduce thermally induced stresses caused by CTE mismatch, thereby reducing the possibility of cracks and improving adhesion and mechanical durability. Porosity can be measured, for example, by using a scanning electron microscope (SEM) and comparing the proportion of the surface occupied by pores to the total surface. In various embodiments, the porous inorganic layer can have a porosity of at least or about 15%, 20%, 40%, 50%, 60%, or greater (e.g., 25% to 30%).

[0130] A relatively high level of porosity in the second decorative layer 250 may tend to reduce the adhesion of the second decorative layer 250 to the first glass interlayer 200, which may reduce scratch resistance and color depth. For example, it has been observed that when the second decorative layer 250 is porous, the second decorative layer 250 may exhibit a gray appearance after firing, even if the enamel is initially black. It has been found that this grayness is reduced after lamination via interaction with the material of the interlayer 230 (e.g., the polymer material may at least partially flow into some of the pores during lamination, resulting in the automotive glazing 130 having a desired appearance).

[0131] although Figure 2 The illustrated embodiment illustrates the automotive glass window 130 as a flat structure (e.g., the first glass interlayer 200 and the second glass interlayer 220 are planar shapes), but it should be understood that embodiments in which the automotive glass window 130 includes a curved shape are also contemplated and within the scope of the present disclosure. In an embodiment, the automotive glass window 130 exhibits at least one curvature, the at least one curvature including a radius of curvature in the range of 300 mm to about 10 m along at least a first axis. In an embodiment, the automotive glass window 130 exhibits at least one curvature, the at least one curvature including a radius of curvature in the range of 300 mm to about 10 m along a second axis transverse to (particularly perpendicular to) the first axis.

[0132] In an embodiment, the curvature is introduced into at least one of the first glass interlayer 200 and the second glass interlayer 220 through a heat treatment. The heat treatment may include a sagging process that uses gravity to shape the first glass interlayer 200 or the first and second glass interlayers 200 and 220 while heating. In the sagging step, the glass interlayer (e.g., the first glass interlayer 200) is placed on a mold with an open interior, heated in a furnace (e.g., a box furnace or an annealing furnace), and allowed to gradually sag into the open interior of the mold under the influence of gravity. In one or more embodiments, the heat treatment may include a pressing process that uses a mold to shape the first glass interlayer 200 or the first and second glass interlayers 200 and 220 after or while heating. In some embodiments, two glass interlayers (e.g., the first and second glass interlayers 200 and 220) are formed together in a "paired forming" process. In such a process, one glass interlayer is placed on top of another glass interlayer to form a stack placed on a mold (which may also include an intermediate release layer). In an embodiment, in order to facilitate the pair forming process, the pair forming temperature (10 11 The temperature of the anchoring place) is greater than the first glass interlayer 200.

[0133] In one or more embodiments, the mold used during the paired sagging may have an open interior for the sagging process. Both the stack and the mold are heated by placing them in a furnace, and the stack is gradually heated to the bending or sagging temperature of the glass interlayer. During this process, the interlayer is formed together into a curved shape. Advantageously, at least some of the borosilicate glass compositions included herein are formed at 10 11 The viscosity curve at a viscosity of 10 poise is similar to the viscosity curve of the glass used for the second glass interlayer 220, allowing the use of existing equipment and technology.

[0134] According to an exemplary embodiment, the heating time and temperature are selected to achieve the desired degree of curvature and final shape. Subsequently, the glass interlayer or multiple glass interlayers are removed from the furnace and cooled. For glass interlayers formed in pairs, the two glass interlayers are separated, reassembled with an interlayer (e.g., interlayer 230) between the glass interlayers, and heated, for example, under vacuum, to seal the glass interlayer and the interlayer together to form a laminate.

[0135] In an embodiment, only one glass interlayer (e.g., the first glass interlayer 200) is bent using heat (e.g., by a sagging process or a pressing process), while the other glass interlayer (e.g., the second glass interlayer 220) is bent using a cold forming process by pressing the glass interlayer to be bent to conform to a glass interlayer that has been bent at a temperature less than the softening temperature of the glass composition (more particularly, at a temperature of 200° C. or less, 100° C. or less, 50° C. or less, or at room temperature). The pressure to cold-form the glass interlayer relative to the other glass interlayer may be provided by, for example, vacuum, mechanical pressing, or one or more clamps. The cold-formed glass interlayer may be held in conformity with the bent glass interlayer via an interlayer and / or mechanical clamping or coupling thereto.

[0136] In an embodiment, the modified enamel cured as described herein for the second decorative layer 250 is deposited onto the first glass interlayer 200 before bending the first glass interlayer 200. As described herein, the softening temperature of the enamel used to form the second decorative layer 250 may be less than or approximately equal to 700° C., 650° C., 600° C., 570° C., 550° C., 525° C., 500° C., 475° C., or approximately equal to 450° C. Typical bending temperatures for the first glass interlayer 200 (e.g., 10 11 The temperature of the second major surface 204 may be greater than or equal to the softening temperature associated with the enamel in the second decorative layer 250. Therefore, the enamel may be fired during the bending process and fused to the second major surface 204 to form the second decorative layer 250, thereby improving process efficiency.

[0137] Figure 3 An exemplary embodiment of a curved glass laminate 300 is depicted. As indicated by the incorporation of similar reference numerals, the curved glass laminate 300 is structurally similar to the curved glass laminates described herein with respect to FIG. Figure 1 to Figure 2 Similar to the automotive glass window 130. Figure 3 It can be seen that the second major surface 204 of the first glass interlayer 200 has a first depth of curvature 310, which is defined as the maximum depth from the plane (dashed line) of the second major surface 204. In the embodiment of the curved second glass interlayer 220, the second major surface 224 of the second glass interlayer 220 has a second depth of curvature 320, which is defined as the maximum depth from the plane (dashed line) of the second major surface 224.

[0138] In an embodiment, one or both of the first depth of curvature 310 and the second depth of curvature 320 is about 2 mm or greater. The depth of curvature may be defined as the maximum distance of the orthogonal distance of a surface from a plane defined by a point on the perimeter of the surface. For example, one or both of the first depth of curvature 310 and the second depth of curvature 320 may range from about 2 mm to about 30 mm. In an embodiment, the first depth of curvature 310 and the second depth of curvature 320 are substantially equal to each other. In one or more embodiments, the first depth of curvature 310 is within 10% of the second depth of curvature 320, more particularly within 5% of the second depth of curvature 320. For illustration, in an example where the second depth of curvature 320 is about 15 mm, the first depth of curvature 310 may range from about 13.5 mm to about 16.5 mm (or within 10% of the second depth of curvature 320).

[0139] In an embodiment, the first depth of curvature 310 is induced in the first glass interlayer 200 by hot forming (e.g., the first glass interlayer 200 can be bent by gravity sagging), and the second depth of curvature 320 is induced in the second glass interlayer 220 by cold forming. In an embodiment, the first depth of curvature 310 and the second depth of curvature 320 are induced by hot bending the first glass interlayer 200 and the second glass interlayer 220 (e.g., in a common bending process or in a process where the interlayers are bent independently of each other).

[0140] refer to Figure 4 , a flow chart of a method 400 for manufacturing a glass laminate according to an exemplary embodiment of the present disclosure is shown. For example, the method 400 can be used to manufacture the glass laminate described herein. Figure 3 The curved glass laminate 300. Therefore, reference will be made to Figures 2 to 3 Various components are shown to help describe the method. It should be understood that alternative methods may be used to form the curved glass laminate 300. In addition, the method 400 may be used to form laminates other than the curved glass laminate 300.

[0141] At block 402, a first glass substrate is provided. Figure 2As described herein, the first glass substrate can take the form of a first glass interlayer 200. For example, the first glass substrate initially provided can take the form of a planar glass sheet comprising one of the borosilicate glass compositions described herein. The first glass substrate can be manufactured or commercially purchased. Any suitable glass forming technology can be used to manufacture the first glass substrate. The glass forming technology used may depend on the borosilicate glass composition, as some compositions may be incompatible with certain glass forming technologies. However, embodiments are contemplated in which the first glass substrate is formed by a suitable downward draw or float process. The first glass substrate can be formed to have a thickness within any range described herein with respect to the first glass interlayer 200.

[0142] At frame 404, a mixture is prepared for depositing the second decorative layer 250 directly on the second major surface 204. The mixture may include an enamel (e.g., a ceramic enamel), the enamel including a glass or ceramic glass frit dispersed in a suitable medium, a colorant component, and optional additives. The enamel may include the formulations described herein for the second decorative layer 250. The enamel (before curing) may be modified by adding any combination of low CTE additive components described herein with additional media. Any glass ceramic or ceramic described herein may be mixed with the uncured enamel using a suitable ratio so that after the enamel is cured, the second decorative layer 250 includes a CTE that substantially matches the CTE of the first glass substrate within the range described herein. Pigments may also be added to the enamel in the case where the low CTE additive component introduces undesirable color.

[0143] When the low CTE additive component is added to the mixture, a dispersing device having a toothed blade rotating at an initial rate (e.g., between 1000 rpm and 2000 rpm) can be used to mix the enamel. After the low CTE additive component is added to the enamel, an additional medium can be added to the mixture to control the viscosity. The additional medium can be the same medium as the medium incorporated into the original enamel and is added to the formulation in an amount equal to the weight of the low CTE additive component and any pigment to keep the total solid content in the formulation close to the original enamel. After adding the medium, the toothed blade can be rotated at an increased rate (e.g., at least 8000 rpm) for at least 10 minutes to obtain proper dispersion of the additional component. The tank temperature should be maintained below 40°C to avoid solvent evaporation or medium degradation. After dispersion, the fineness of the grind is controlled using the Hegman specification and can be less than or equal to the target value given for the original enamel. Use a rheometer at 5s -1 The final viscosity of the modified enamel measured at shear rate may range from 500 mPa.s to 50,000 mPa.s (eg, approximately 10,000 mPa.s), and may therefore be compatible with screen printing application methods.

[0144] At block 406, the modified enamel is deposited onto the second major surface 204 of the first glass interlayer 200. Deposition may be performed using any suitable technique (e.g., screen printing, spraying, brushing, tape), with the understanding that viscosity adjustment may be required depending on the selected deposition technique (e.g., via the addition of water or an additional medium). At block 408, the modified enamel is cured on the first glass interlayer 200 by heating to a suitable firing temperature (e.g., at least the softening temperature associated with the enamel) to dissolve the solvent and cure the glass frit into a glass fusion matrix around the low CTE additive component. At block 410, the first glass interlayer 200 is formed. In an embodiment, blocks 408 and 410 occur simultaneously because the modified enamels described herein are beneficially compatible with heat bending techniques and can be cured when the first glass interlayer 200 is heated to a forming temperature in a furnace using suitable forming equipment (e.g., a bending ring or mold).

[0145] In block 412, the second glass substrate is laminated to the first glass substrate via the interlayer. For example, in an embodiment, the second glass interlayer 220 having any composition described herein may be provided to have a planar shape. The second glass interlayer 220 may be pressed onto the first glass interlayer 200 with the interlayer 230 therebetween, and when pressure is applied, the stack may be heated to a glass transition temperature associated with the material of the interlayer 230 and then cooled, causing the interlayer 230 to solidify and attach the first glass interlayer 200 to the second glass interlayer 220, so that the second glass interlayer 220 maintains a curved shape matching the first glass interlayer 200. In this example, the first decorative layer 240 may have been formed on the second glass interlayer 220 before the second glass interlayer 220 is laminated to the first glass interlayer 200. In an embodiment, for example, the first decorative layer 240 may be formed of a commercially available enamel applied to the second glass interlayer 220 when flat. In another example, both the first glass interlayer 200 and the second glass interlayer 220 can be thermally formed (e.g., co-sagging at the same time, or bending separately). Embodiments are also contemplated in which one or more of the first decorative layer 240 and the second decorative layer 250 are deposited on a curved surface (e.g., after the first glass interlayer 200 and the second glass interlayer 220 are formed).

[0146] refer to Figure 2 Various exemplary compositions of borosilicate glass included in the first glass interlayer 200 will now be described. Table 1 below describes the compositions and various properties of Examples 1-6.

[0147] Table 1

[0148]

[0149]

[0150] As shown in Table 1, each of the glass compositions exhibits a low temperature coefficient of thermal expansion (LTCTE) of 5.6 ppm / °C or less (more particularly 5.3 ppm / °C or less, and specifically 5.1 ppm / °C or less), obtained by measuring the expansion of the glass between 0°C and 300°C.

[0151] Table 2 below describes additional exemplary borosilicate glass compositions.

[0152] Table 2

[0153]

[0154]

[0155] As shown in Table 2, Examples 12-14 show that increasing the amount of B2O3 can have a density-reducing effect. The above examples include at least 5.5 mol% Na2O+K2O and at least 7.0 mol% Na2O+K2O+MgO+CaO in total. Based on the examples in Tables 1-2, it is believed that embodiments of the present disclosure will exhibit T2O3 formed by fusion. 200P and liquidus viscosity, wherein the total amount of Na2O+K2O+MgO+CaO is at least 7.0 mol%, especially in the case of at least 5.5 mol% Na2O+K2O and at least 1.5 mol% MgO+CaO. It is further believed that embodiments of the present disclosure will exhibit the T required for fusion formation. 200P and a liquidus viscosity wherein Na2O+K2O is at least 8 mol %, regardless of the amounts of MgO and CaO.

[0156] Iron may also be added to borosilicate glass compositions to provide desired optical transmission properties for automotive glazing applications. Table 3 below shows examples of incorporation of various amounts of iron. Any of the following patent applications describe any of the examples: U.S. Provisional Patent Application 63 / 123863, filed on December 10, 2020, entitled “Fusion Formable Borosilicate Glass Composition and Articles Formed Therefrom,” U.S. Provisional Patent Application 63 / 183271, filed on May 3, 2021, entitled “Fusion Formable Borosilicate Glass Composition and Articles Formed Therefrom,” U.S. Provisional Patent Application 63 / 183292, filed on May 3, 2021, entitled “Glass with Unique Fracture Behavior for Vehicle Windshield,” U.S. Patent Application 17 / 363266, filed on June 30, 2021, and U.S. Patent Application 17 / 363267, filed on December 6, 2021, entitled “Glass with Unique Fracture Behavior for Vehicle Windshield,” International patent application PCT / US2021 / 061966 of "Windshield" can be used for the first glass interlayer 200 in various embodiments.

[0157] Table 3

[0158]

[0159] As illustrated in the above examples, in an embodiment, the borosilicate glass composition forming the first glass interlayer 200 includes: an amount of SiO2 in a range of 72 mol% to 80 mol% (e.g., 74 mol% to 80 mol%), an amount of B2O3 in a range of 10 mol% to 20 mol% (e.g., 11 mol% to 20 mol%, 11 mol% to 16 mol%), an amount of Al2O3 in a range of 2 mol% to 6 mol% (e.g., 2.5 mol% to 5 mol%, 3 mol% to 5 mol%), an amount of Na2O in a range of 3 mol% to 8 mol% (e.g., 4 mol% to 8 mol%, 4.5 mol% to 6.5 mol%), an amount of K2O less than the amount of N2O (e.g., such that the ratio of K2O to N2O ranges from 0.1 to 0.75, or from about 0.1 to about 0.45), and less than or equal to 5 mol% of MgO and the total amount of the present correction. In an embodiment, the amount of Na2O may exceed the amount of Al2O3 by at least 1.0 mol% (e.g., at least 1.25 mol% or at least 1.5 mol%). This combination of composition amounts may facilitate forming the first glass interlayer 200 via a fusion forming technique (and thereby achieving the optical distortion performance benefits and scratch resistance associated with such a forming technique) while being formed to be stable and have desired chemical and mechanical durability characteristics.

[0160] Example

[0161] Embodiments of the present disclosure can be further understood from the following examples.

[0162] In the following examples, commercially available enamels from Ferro Corporation were modified by incorporating a low CTE additive component. The starting materials in the following examples are described in Table 4 below.

[0163] Table 4

[0164]

[0165] Five examples (Examples 23-28 and 31) were prepared as described in Table 5 below. The examples are prepared according to the invention Figure 4 The method 400 is for depositing a decorative layer of the composition of the present disclosure on a flat glass substrate. The borosilicate glass composition used in the following examples exhibits a CTE (25-300° C.) of about 45×10 -7 K -1 Each of Examples 23-28 exhibited a porosity of 25% to 30%.

[0166] Table 5

[0167]

[0168]

[0169] For each of the examples described in Table 5, mechanical properties were measured via a ring-to-ring (ROR) test using a 32 mm diameter and a glass thickness of 3.8 mm. The ROR test was conducted according to the ASTM C-1499-03 standard test method for Monotonic Equibiaxial Flexural Strength of Advanced Ceramics at Ambient Temperatures. The Weibull distribution for each of the samples was calculated. The Weibull distribution results for some of the examples are depicted in Figure 5 As shown in the figure, Examples 23 and 26 surprisingly exhibit mechanical properties superior to those of a bare glass substrate (having the same composition but without a decorative layer disposed thereon). As shown in the figure, the Weibull slope of each of Examples 23 and 26 is less than that of the bare glass substrate. In addition, as can be seen from Table 5 above, each of Examples 23-27 and 31 exhibits a B10 value (mechanical load at a breakage probability of 10%) greater than or equal to 60 MPa, while the bare glass substrate exhibits a B10 value of about 47 MPa. Compared to a bare substrate, a glass substrate decorated with enamel of the present disclosure unexpectedly exhibits higher mechanical strength (as shown by a higher B10 value) and excellent reliability (as shown by a smaller Weibull slope parameter). In embodiments, when the glass substrate of the glass article described herein has a thickness greater than or equal to 2.1 mm, the decorative glass article exhibits a B10 value greater than or equal to 60 MPa (e.g., greater than or equal to 65 MPa, greater than or equal to 70 MPa, greater than or equal to 75 MPa, greater than or equal to 80 MPa, greater than or equal to 85 MPa).

[0170] like Figure 5 As shown, the relative example CE1 exhibits worse mechanical properties than the examples 23-27 and the bare glass substrate. -7 K -1, but it is believed that the relatively low mechanical strength is caused by the lack of porosity in the decorative layer. It is believed that due to the relatively low amount of low CTE additive component added (the decorative layer only includes 15 wt % of the low CTE additive component), little porosity is observed in the decorative layer of the relative example CE1. Therefore, in an embodiment, the decorative layer of the glass article described herein can include greater than 15 wt % (e.g., greater than or equal to 16 wt %, greater than or equal to 17 wt %, greater than or equal to 18 wt %, greater than or equal to 19 wt %, greater than or equal to 20 wt %, greater than or equal to 21 wt %, greater than or equal to 22 wt %, greater than or equal to 23 wt %, greater than or equal to 24 wt %, greater than or equal to 25 wt %, greater than or equal to 20 wt % and less than or equal to 50 wt %, greater than or equal to 20 wt % and less than or equal to 45 wt %, greater than or equal to 25 wt % and less than or equal to 45 wt %, greater than or equal to 30 wt % and less than or equal to 40 wt %, and any intermediate ranges) of the low CTE additive component. It is believed that this amount of the low CTE additive component provides a decorative layer in the desired CTE range while still introducing porosity in the decorative layer for excellent mechanical strength properties.

[0171] Referring to Table 5, the CTE of the enamel was measured on the sintered small particles of the modified enamel. In order to measure the CTE, a thin layer of enamel was placed on a glass ceramic sample and then placed in an oven for several hours (120°C) to remove the solvent. After the solvent evaporated completely, the enamel became a dry powder. Then, it was crushed in an agate bowl to obtain a fine powder. The powder was pressed into smaller particles using a granulator and sintered at 625°C for 7 minutes. The CTE of the sintered small particles was measured using TMA. This measurement was completed using TA Instruments' TMA Q400 EM. As shown in Table 5, each of Examples 23-27 exhibited a CTE less than or equal to 50×10 -7 K -1 The CTE of each decorative layer according to the example is in the range of 34×10 -7 K -1 Up to 50×10 -7 K -1 Examples 23 and 24 include CTE values ​​closest to the glass substrate. Example 23 exhibits the highest B10 value, while Example 24 exhibits the lowest Weibull slope.

[0172] The color of each of Examples 23, 26, and 27 was measured by illuminating the sample at a 10° viewing angle using a D65 illumination source. The integrated visible light transmittance of each of these examples over the visible spectrum was also measured. As shown, for each of these examples, the L* value was less than 15, and in some cases, even less than 10, or even less than 5. The integrated visible light transmittance before lamination was less than or equal to 2.0%, less than or equal to 1.5% in some cases, and less than or equal to 1.0% in some cases. After lamination, the integrated visible light transmittance was slightly lower than before lamination because the PVB interlayer filled at least some of the holes in the decorative layer. The laminate was an inner interlayer of 0.7 mm thick aluminosilicate glass, 0.76 mm thick PVB interlayer, and a 3.8 mm outer glass interlayer of a borosilicate glass composition as described herein. The decorative layer was disposed on the outer interlayer adjacent to the interlayer.

[0173] Using Altisurf TM The thickness of the decorative layer of each of the samples was measured using a 2 mm confocal sensor with the following metrology filters. The software generates a distribution curve: a polynomial of degree 3 is used to remove shape defects and a Gaussian robust filter is used to remove measurement artifacts. An exemplary thickness distribution curve for example CE2 is shown in Figure 6 As shown, the measured thickness value is 12.24 μm. As shown, due to the porosity in the decorative layer, the surface height deviates from the average obtained.

[0174] Fig. 7A , Figure 7B ,and Figure 7C Scanning electron microscope images of Example 23, Example 26, and Relative Example CE1 are depicted. Fig. 7A This is image 700 of Example 23. Figure 7B This is the image of Example 26. Figure 7C is an image relative to Example CE1. As shown, each of Examples 23 and 26 exhibits porosity and contains pores having a maximum diameter greater than 1.0 μm. Both Examples 23 and 26 exhibit pores having a maximum pore diameter greater than 2.0 μm. Fig. 7A As shown, Example 23 includes a hole 701 having a maximum diameter 703 of approximately 4.0 μm. Figure 7B As shown, Example 26 includes a hole 705 having a maximum diameter 707 of approximately 5.0 μm. As used herein, "maximum diameter" refers to the length of the longest straight line contained in the volume of the hole that does not intersect the hole boundary. Such an end of the maximum diameter may also occur at the surface of the glass substrate.

[0175] like FIG. 7A to FIG. 7BAs shown, each of Examples 23 and 26 exhibits a hole (e.g., a void without the material of the decorative layer) at the interface between the glass substrate and the decorative layer (Example 23 includes an interface hole 710, while Example 26 includes an interface hole 712). That is, in these examples, the interface between the glass substrate and the decorative layer does not include a continuous contact area between the glass and the cured enamel, but rather a discontinuous contact area. The rupture of the contact area between the glass substrate and the decorative layer may help provide excellent mechanical strength properties for the decorative glass article.

[0176] refer to Figure 7C , relative example C1 includes a non-porous decorative layer 720 that does not have any pores with a maximum diameter greater than 1.0 μm. Therefore, the interface between the glass substrate and the non-porous decorative layer 720 is a continuous contact area between the glass and the material of the decorative layer. It is believed that this continuous contact reduces the mechanical strength of the glass substrate by increasing the possibility of cracks forming in the decorative layer, resulting in more defects.

[0177] To investigate the relationship between the decorative layer and porosity, additional exemplary decorative layers were formed on soda-lime-silicate glass substrates. The glass substrates in these examples consisted of approximately 90×10 -7 K -1 Three examples were prepared and the details are provided in Table 6 below.

[0178] Table 6

[0179]

[0180]

[0181] As shown in Table 6, Example 28 consisted of a bare glass substrate, Example 29 consisted of a glass substrate decorated with a commercially available enamel to provide a non-porous decorative layer, and Example 30 consisted of a glass substrate with a modified decorative enamel having a pigment additive to provide a porous decorative layer. ROR tests were performed on each sample, and the results are shown in Table 6. Figure 8 As shown. As shown, the porous enamel exhibits higher B10 values ​​than the non-porous examples. In addition, the deposition of the enamel appears to result in a higher slope of the Weibull distribution, indicating improved reliability. With respect to the B10 values, Example 30 achieves superior performance to Example 29, indicating the benefit of the porous decorative layer.

[0182]

[0013] Embodiments of the present disclosure can be further understood from the following information.

[0183] The decorative layers described herein may generally include a base enamel (e.g., including one or more of any of the glass frit components, colorant components, and additive components described herein) and one or more porosity inducing components (e.g., any of the low CTE additive components described herein (e.g., β-eucryptite phase of LiALSiO4), other fillers (e.g., alumina, zeolites), and / or pigment additives that promote the formation of porosity in the decorative layer after curing). In embodiments, it is preferred that the decorative layer exhibit a porosity greater than or equal to 5% (e.g., greater than or equal to 10%, greater than or equal to 15%, greater than or equal to 20%, greater than or equal to 25%, greater than or equal to 30%) after curing. The porosity may be determined by SEM image analysis (averaging four images at different non-overlapping locations of the same sample). When measuring the porosity of the examples described herein, each image in the SEM measurement captured a length of about 55 μm of the decorative layer. It has been found that a decorative layer exhibiting such porosity can be printed on up to about 23×10 -7 K -1 In an embodiment, when incorporating various laminate structures that meet the aforementioned porosity and ΔCTE requirements, the glass articles including the porous decorative layer described herein can achieve a B5 value greater than or equal to 45 MPa (e.g., greater than or equal to 50 MPa, greater than or equal to 55 MPa, greater than or equal to 60 MPa, greater than or equal to 65 MPa, greater than or equal to 70 MPa, or even greater than or equal to 75 MPa).

[0184] Even with such porosity in the decorative layers described herein, the glass articles described herein have been found to exhibit a desirable opaque appearance. In embodiments, after lamination, in the region where the interlayer material (e.g., polymer interlayer (e.g., PVB)) fills at least some of the pores in the decorative layer (as a result of lamination), the glass articles described herein exhibit a CIELAB L* value of less than or equal to 12 (e.g., less than or equal to 11, less than or equal to 10, less than or equal to 9, less than or equal to 8, less than or equal to 7). The glass articles described herein may also exhibit a maximum ΔE value calculated between two different locations on the article where the decorative layer is disposed and at least partially fills the pores, calculated using the CIE76 formula, of less than or equal to 3.0 (e.g., less than or equal to 2.5, less than or equal to 2.0, less than or equal to 1.5, less than or equal to 1.0). In embodiments, the glass article exhibits an integrated visible light transmittance (in the region where the decorative layer is disposed) of less than or equal to 2.0% (e.g., less than or equal to 1.8%, less than or equal to 1.6%, less than or equal to 1.4%, less than or equal to 1.2%, less than or equal to 1.0%, less than or equal to 0.8%, less than or equal to 0.6%, less than or equal to 0.4%, less than or equal to 0.2%, less than or equal to 0.1%) for light with a normal incidence of 400 nm to 700 nm on the glass article. Thus, after lamination, the decor provides a desirable opaque and uniform appearance while helping to conceal various components that may be disposed behind the glass article (e.g., in an automotive visor).

[0185] In embodiments, the decorative articles described herein may include one or more regions where the pores in the decorative layer are not filled with the polymeric material of the interlayer (e.g., the glass article may not be a laminate, or the interlayer material may not have flowed into the pores during lamination). Such regions may exhibit an L* value of less than or equal to 30 and may provide a variety of appearances desired for particular applications.

[0186] In one aspect, the glass articles described herein pass standard weathering tests (e.g., baking test, boiling test, and UV resistance) for the automotive industry according to standard ANSI Z26. To facilitate passing such tests, when the decorative glass article is incorporated into a laminate, the outer edges of the porous decorative layer can be encapsulated in the polymeric material of the interlayer material.

[0187] To further understand the performance attributes of the decorative layers described herein, additional examples were constructed and various mechanical and optical performance properties were analyzed. The first set of examples was constructed on 2.1 mm thick soda lime glass sheets. Fig. 9A An exemplary glass article having a nonporous decorative layer (having the same composition as the decorative layer described above with respect to Example 29) is depicted. Fig. 9A In the example shown, the nonporous decorative layer and the glass exhibit approximately 10×10 -7 K -1 ΔCTE. Fig. 9B An exemplary glass article having a porous decorative layer (having the same composition as the decorative layer described above with respect to Example 30) is depicted. Fig. 9B In the example shown, the ΔCTE between the porous decorative layer and the glass is about 5×10 -7 K -1 )(porosity less than 20% but greater than 5%).

[0188] Fig. 9A and Fig. 9B The examples shown as well as the bare soda lime glass substrate were subjected to ROR testing according to ASTM C-1499-03 with a diameter of 32 mm. Fig. 9C As shown. As shown, consistent with the results of Examples 28, 29, and 30 above, the examples with porous decorative layers exhibit mechanical strength superior to that of the examples with non-porous decorative layers. In fact, the bare substrate exhibits a B5 value of 65 MPa, the example with the non-porous decorative layer exhibits a B5 value of 41 MPa, and the example with the porous decorative layer exhibits a B5 value of 62 MPa. These results indicate that the porous decorative layer unexpectedly does not significantly impair the mechanical strength of the glass substrate. In fact, the samples with the porous decorative layer exhibit a B5 value greater than or equal to 45 MPa, indicating that the decorative layer described herein provides excellent mechanical properties compared to certain existing decorative materials. Compared to a bare, undecorated substrate, the porosity in the decorative layer results in a decrease in mechanical strength of less than 10%, or even improves the mechanical strength results. This result indicates that the porous decorative layer can be useful even when used to decorate a glass substrate that is not chemically strengthened, such as a soda-lime silicate glass composition in an automotive glazing (e.g., the soda-lime glass can be used as an exterior and / or interior interlayer in the glazing and decorated by one of the decorative layers described herein).

[0189] In the borosilicate glass composition described herein with respect to Example 22 (comprising approximately 45.2×10 -7 K -1 Another set of exemplary decorative layers was formed on a 3.8 mm thick glass substrate formed with a CTE of 1.1 mm. Fig. 10A A first porous decorative layer on borosilicate glass is depicted. The first porous decorative layer has the same composition as the decorative layer in Example 31. The ΔCTE of the first porous decorative layer to the glass substrate is about 3×10 -7 K -1 . Fig. 10BA second porous decorative layer on borosilicate glass is depicted. The second porous decorative layer comprises Ferro 13316 base enamel and 25 wt% zeolite as a porosity inducing component. The ΔCTE of the second porous decorative layer to the glass substrate is about 23×10 -7 K -1 Both examples exhibit porosities between 25% and 30%.

[0190] Fig. 10A and Fig. 10B The examples shown are similar to those described above. Fig. 9A and Fig. 9B The ROR test was performed in the same manner as in . A bare substrate of borosilicate glass was also tested. A glass substrate decorated with a non-porous decorative layer consisting of a Ferro 14316 base enamel including 15 wt. % of 118VTC particles was also tested. Fig. 10A The results for the examples shown, bare substrate, and non-porous decorative layer are presented in Fig. 10C As shown in the figure, the example with the porous decorative layer exhibits better mechanical strength than the example with the non-porous decorative layer. In fact, the bare substrate exhibits a B5 value of 68 MPa, the example with the non-porous decorative layer exhibits a B5 value of 26 MPa, and the example with the porous decorative layer exhibits a B5 value of 71 MPa. Fig. 10B The example shown was also tested and showed a B5 value of 85 MPa. Surprisingly, despite the 23×10 -7 K -1 The ΔCTE of the glass substrate is relatively high, but the decorative layer with the zeolite additive shows excellent mechanical strength results. This result unexpectedly demonstrates that a porous decorative layer with a ΔCTE relative to the glass substrate of greater than or equal to 10.0 (e.g., greater than or equal to 11.0, greater than or equal to 12.0, greater than or equal to 13.0, greater than or equal to 14.0, greater than or equal to 14.0, greater than or equal to 15.0, greater than or equal to 16.0, greater than or equal to 17.0, greater than or equal to 18.0, greater than or equal to 19.0, greater than or equal to 20.0, greater than or equal to 21.0, greater than or equal to 22.0, greater than or equal to 23.0) can be used while still showing acceptable mechanical properties.

[0191] On borosilicate glass (with a thickness of 3.8 mm) according to Example 22 a further porous decorative layer was built up which comprised Ferro 14316 as base enamel and was modified with 35 wt. % of aluminium oxide particles as porosity-inducing component. Fig.11 The porous decorative layer exhibits a porosity of about 30% and a void volume of about 30×10 -7 K -1The ROR strength test was performed in a manner consistent with the other examples and determined Fig.11 The examples shown exhibited a B5 value of approximately 24 MPa, which is similar to the examples with nonporous decorative layers. These results indicate that the porosity may not be sufficient to overcome the porosity greater than or equal to 30×10 -7 K -1 The relatively high ΔCTE value.

[0192] To determine the amount of porosity desired for the decorative layer described herein, multiple samples were constructed on the borosilicate silicate glass composition described herein with respect to Example 22. These samples had a porous decorative layer formed using different amounts of zeolite ZSM-5 as a porosity inducing component. The particle size (d50) of the zeolite particles was between 2.5 μm and 3.0 μm. Fig. 12A Each of the samples is plotted in FIG. As shown, the porosity in the decorative layer tends to increase in proportion to the amount of zeolite added. The samples were subjected to ROR testing using a method consistent with the other examples. The B5 value for each of the samples was determined and plotted as a function of the porosity for each of the samples. The results are plotted in Fig. 12B As shown, the decorative layers having porosities between 6.7% and 18.5% exhibit relatively low B5 values ​​of less than 25 MPa. When the porosity is above 18.5%, the B5 value increases quasi-linearly as a function of porosity. Therefore, for these specific examples, it was determined that the decorative layer exhibiting at least 25% porosity may exhibit a target B5 value of at least 55 MPa. The example with 25 wt.% zeolite in the decorative layer still exhibits a B5 value of about 23×10 -7 K -1 It is believed that the zeolite as a porous filler (the zeolite particles themselves contain pores ranging in size from 1 nm to 10 nm) may contribute to these favorable results.

[0193] Fig.13A Depicted is an exemplary porous decorative layer on a borosilicate glass substrate prior to lamination. As shown, this example exhibits a gray appearance (L* value of about 30) when viewed from the glass side. Fig. 13B The same examples are depicted after lamination with another glass substrate via a PVB interlayer. In these examples, the borosilicate glass is 3.8 mm and the interlayer material is a PVB layer with a thickness of 0.76 mm. The interlayer material is applied between the decorated borosilicate glass substrate and the aluminosilicate glass substrate with a thickness of 0.7 mm. The stack is degassed at 118°C and 0.95 bar pressure and subsequently heated to 140°C in an autoclave at 13 bar pressure. As shown in the figure, during lamination, the interlayer material flows into the pores of the decorative layer and darkens the appearance of the article. After lamination, when the interlayer material is removed from the pores of the decorative layer, the appearance of the article is darkened. Fig.13A When viewed from the same glass side, the article exhibits an L* value of less than 8, which is desirable for automotive applications. Despite the presence of porosity, this example demonstrates how the porous decorative layers described herein can achieve advantageous appearance attributes.

[0194] In embodiments, the porous decorative layer described herein may cover at least 5% (e.g., at least 6%, at least 7%, at least 8%, at least 9%, at least 10%, at least 15%, at least 20%, at least 25%, or greater than or equal to 10% and less than or equal to 30%) of the total surface area (the major surface disposed thereon) of the glass article. For example, in automotive applications, the surface area of ​​the glass article (e.g., measured on the outer surface) may be at least 0.25 m 2 (For example, at least 0.5m 2 , at least 0.75m 2 , at least 1.0m 2 , at least 1.5m 2 , at least 2.0m 2 , at least 2.5m 2 ). Therefore, the porous decorative layer can cover at least 0.00125m 2 In an embodiment, the glass article may have a surface area greater than or equal to 2.0 m 2 The porous decorative layer may have a surface area of ​​at least 0.1 m 2 or at least 0.2m 2 The surface area covered by the decorative layer can extend around the perimeter of the glass article (e.g., extending inward from an adjacent edge or a peripheral edge of the glass article to form a decorative border of the glass article on a major surface). Despite the porous decorative layer covering such a large area, the glass article can still exhibit the mechanical strength properties described herein.

[0195] Further samples were constructed to determine the effect of the porosity inducing component particle size. A first set of samples was formed using a decorative layer having the composition described herein with respect to Example 31 and a 118 VTC additive having different d50 particle sizes. Fig.14A As shown, the first example includes 118VTC that is wet milled and dried to provide a d50 particle size of 1 μm. Fig. 14B As shown, the second example includes 118VTC jet milled to provide a d50 particle size of 2.5 μm. Fig. 14CAs shown, the third example includes 118VTC jet milled to provide a d50 particle size of 5 μm. The first example has a porosity of about 26.8%. The second example has a porosity of about 27.3%. The third example has a porosity of about 26.4%. As shown, reducing the particle size of the porosity inducing component (or in this case the low CTE additive component) reduces the average pore size while keeping the overall porosity relatively constant.

[0196] The ROR tests were conducted in a manner consistent with the other examples, where the decorative layers were deposited on borosilicate glass articles having a thickness of 3.8 mm. The B5 values ​​and Weibull ratio values ​​as a function of the d50 particle size are plotted in Fig.15A As shown in the figure, as the additive particle size increases, the B5 value and the Weibull ratio value both decrease. Similar tests were performed on a second set of examples having a decorative layer having the composition described herein with respect to Example 23. FIG. 13A to FIG. 1 For the first set of examples shown in 3C, the particle size of the 118VTC additive was varied in the same manner (d50 particle size was 1 μm, 2.5 μm, and 5 μm, respectively). ROR tests were performed on the second set of examples, and the B5 value and Weibull ratio as a function of particle size were plotted in Fig. 15BAs shown, the B5 values ​​and Weibull ratios for the second set of examples also tend to decrease as the additive particle size increases. Based on these results, it may be preferred that the porosity-inducing additive component have a d50 particle size of less than or equal to 10 μm (e.g., greater than or equal to 0.01 μm and less than or equal to 10 μm, or more preferably less than or equal to 5 μm) to avoid adverse effects on mechanical properties. In an embodiment, the particle size of the porosity inducing additive component may be greater than or equal to 0.01 μm and less than or equal to 10 μm (e.g., greater than or equal to 0.1 μm and less than or equal to 10 μm, greater than or equal to 0.5 μm and less than or equal to 10 μm, greater than or equal to 1.0 μm and less than or equal to 10 μm, greater than or equal to 0.01 μm and less than or equal to 5 μm, greater than or equal to 0.1 μm and less than or equal to 5 μm, greater than or equal to 0.5 μm and less than or equal to 5 μm, greater than or equal to 1.0 μm and less than or equal to 5 μm, greater than or equal to 0.01 μm and less than or equal to 2.5 μm, greater than or equal to 0.1 μm and less than or equal to 2.5 μm, greater than or equal to 0.5 μm and less than or equal to 2.5 μm, greater than or equal to 1.0 μm and less than or equal to 2.5 μm). In an embodiment, the porosity inducing component has a d50 particle size greater than or equal to 1.0 μm and less than or equal to 5 μm. Maintaining the particle size within these ranges can advantageously prevent the decorative layers described herein from adversely affecting the mechanical properties of the glass articles described herein (e.g., the decorative layer does not reduce the B5 or B10 value of the bare glass substrate by more than 10%).

[0197] To evaluate the effect of the particle size of the porosity inducing component on the optical performance, the integrated optical transmittance of the second set of samples was measured before and after lamination to another interlayer of aluminosilicate glass via a PVB interlayer. Light from a D65 illumination source was transmitted through the samples to measure the optical transmission properties. The results are plotted in Fig.16 As shown in the figure, the integrated optical transmittance increases with the increase of the particle size of the porosity inducing component before and after lamination. More specifically, after lamination, the samples having a d50 particle size of less than 5 μm exhibited an optical transmittance of less than 0.5%. Each of the samples also exhibited an increase in the integrated optical transmittance according to lamination. Fig.16 As shown, the difference before and after lamination is smallest when the particle size is smallest. In other words, when the particle size of the porosity inducing component is smallest, the difference in optical transmission produced by lamination is smallest. This indicates that smaller particle sizes (e.g., d50 particle sizes of less than 5 μm, less than 3 μm, or less than 2 μm) may be beneficial from the perspective of mechanical and optical performance.

[0198] In an embodiment, the porous decorative layer described herein may be characterized as including at least 15% by volume of a porosity-inducing component (e.g., a low CTE additive component, a pigment, or other filler (e.g., alumina or zeolite)). In an embodiment, the porous decorative layer described herein may include an amount of porosity-inducing component particles (e.g., one or more of a low CTE additive component, a pigment additive, or any other suitable material described herein) constituting 15% to 40% by volume of the porous decorative layer. Such an amount may ensure sufficient porosity to provide the desired mechanical performance attributes described herein. The term "porous decorative layer" may be used interchangeably herein with "porous inorganic layer".

[0199] The present disclosure contemplates producing a porous decorative layer via a variety of different techniques. The porosity-inducing components described herein (e.g., low CTE additive components, alumina, pigment additives, or other suitable materials) are typically added to the enamel (uncured) in an amount sufficient to induce porosity after firing (e.g., above the critical pigment volume concentration for pigments and similar amounts for other porosity-inducing components). The amount of porosity-inducing component required to induce porosity in the decorative layer can vary depending on the composition of the enamel (e.g., the composition of the glass frit component and / or the amount of pigment or other filler already present in the enamel). In embodiments, rather than introducing particles of the porosity-inducing component into the enamel, porosity can be created via the introduction of an organic pore former material, which will create porosity after thermal degradation during firing. For example, the organic material can be burned off during firing and leave voids in the decorative layer in any amount described herein. Examples formed using this technique may not include porosity-inducing component particles in the cured decorative layer to the same extent as other examples that rely solely on porosity-inducing component particles to induce porosity.Any suitable method of forming porosity in a frit-based decorative layer may be used.

[0200] As used herein, the term "disposed" includes coating, depositing, and / or forming a material on a surface using any method known in the art. The disposed material may constitute a layer as defined herein. The phrase "disposed on..." includes the case where the material is formed onto a surface so that the material is in direct contact with the surface, and also includes the case where the material is formed on a surface with one or more intervening materials located between the disposed material and the surface. The one or more intervening materials may constitute a layer as defined herein.

[0201] The ranges represented herein may be from "about" one particular value and / or to "about" another particular value. When such a range is represented, another embodiment includes from a particular value and / or to another particular value (i.e., the range includes the endpoints that are clearly stated). Similarly, when a value is represented in an approximate manner using the preposition "about", it will be understood that the particular value will form another embodiment. For example, the range "from about 1 to about 2" also clearly includes the range "from 1 to 2". Similarly, the range "about 1 to about 2" also clearly includes the range "1 to 2". It can be further understood that each endpoint of the range is clearly related to the other endpoint and is independent of the other endpoint.

[0202] Directional terms used herein (eg, up, down, right, left, front, back, top, bottom) are used only with reference to the drawings depicted and are not intended to imply an absolute orientation.

[0203] Unless otherwise expressly stated, any method described herein is not to be construed as requiring that its steps be performed in a particular order, nor does it require a particular orientation of any device. Therefore, in the event that a method claim does not actually recite the order of its steps, or any device claim does not actually recite the order or orientation of independent components, or does not specifically state in the claim or narrative that the steps are limited to a particular order, or does not recite a particular order or orientation of components of the device, no order or orientation is to be inferred in any way in any respect. This applies to any possible non-expressive basis for description, including: logical themes for the arrangement of steps, operational flows, order of components, or orientation of components; general meaning derived from grammatical organization or punctuation; and the number or type of embodiments described in the specification.

[0204] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a" component includes aspects having two or more components unless the context clearly dictates otherwise.

[0205] As shown in the various exemplary embodiments, the construction and arrangement of components, assemblies, and structures are illustrative only. Although the present disclosure describes only a few embodiments in detail, many modifications are possible (e.g., changes in the size, dimensions, structure, shape, and proportion of various components, the values ​​of parameters, mounting arrangements, the use of materials, colors, orientations), without substantially departing from the novel teachings and advantages of the objects described herein. The materials (e.g., glazing disclosed herein) can be used for glazing in architectural applications (e.g., windows, partitions), or can be used in other ways (e.g., for packaging (e.g., containers)). The order or sequencing of any process, logical algorithm, or method steps can be changed or reordered according to alternative embodiments. Other substitutions, modifications, changes, and omissions can also be made in the design, operating conditions, and arrangements of the various exemplary embodiments without departing from the scope of the present technology.

Claims

1. A decorative glass product, comprising: a glass substrate comprising a first main surface and a second main surface disposed opposite to the first main surface; as well as A decorative layer adhered to at least a portion of the second major surface, the decorative layer comprising: a glass flux matrix; and A plurality of holes, wherein: The glass substrate comprises a thickness greater than or equal to 2.1 mm, The decorative layer includes a CTE of 23×10 -7 K -1 The coefficient of thermal expansion ("CTE") within When at least ten of the decorative glazings are subjected to a ring-to-ring strength test according to ASTM C-1499-03, the decorative glazings exhibit a B5 value greater than or equal to 45 MPa.

2. The decorative glass article according to claim 0, wherein the porosity is greater than or equal to 5%.

3. The decorative glass article according to any one of claims 1 to 2, wherein the B5 value is greater than or equal to 55 MPa.

4. The decorative glass article according to any one of claims 1 to 3, wherein the decorative layer comprises at least 15 volume % of the porosity-inducing component particles.

5. The decorative glass article of claim 4, wherein the porosity-inducing component particles include a plurality of particles of at least one of beta eucryptite ceramic, alumina, a pigment additive, and a zeolite.

6. The decorative glass article of claim 5, wherein the plurality of particles comprises a d50 particle size greater than or equal to 1 μm and less than or equal to 5 μm.

7. The decorated glass article of any one of claims 1 to 6, wherein the decorative layer covers greater than or equal to 5% of the total surface area of ​​the second major surface.

8. The decorative glass article according to any one of claims 1 to 7, wherein at least one of the following is present: The glass substrate is not chemically strengthened, and The glass substrate is formed of a soda-lime-silicate glass composition.

9. The decorated glass article of any one of claims 1 to 8, wherein the decorative layer is encapsulated in a polymer material.

10. The decorative glass article according to any one of claims 1 to 9, wherein the difference between the CTE of the decorative layer and the CTE of the glass substrate is greater than or equal to 15×10 -7 K -1 .

11. The decorative glass article of any one of claims 1 to 10, wherein the decorative layer comprises greater than or equal to 20 wt % and less than or equal to 40 wt % of low CTE additive component particles, wherein at least some of the low CTE additive component particles comprise less than or equal to 10×10 -7 K -1 CTE.

12. The decorative glass article of claim 11, wherein each of the plurality of low CTE additive component particles comprises glass, glass frit, glass enamel, ceramic enamel, glass ceramic, or ceramic material.

13. The decorated glass article of any one of claims 1 to 12, wherein the decorative layer comprises greater than or equal to 5 wt. % of a pigment additive.

14. The decorative glass article of claim 13, wherein the pigment additive comprises at least one of a CuCr-based pigment, a MgFe-based pigment, and a FeCrCoNi-based pigment.

15. The decorative glass article of any one of claims 11-14, wherein the low CTE additive component particles and the pigment additive, where present, comprise an average particle size of less than or equal to 10 μm.

16. The decorative glass article of any one of claims 1-15, further comprising a second glass substrate and an interlayer disposed between the second glass substrate and the second major surface, wherein a polymer material of the interlayer is present in the plurality of pores.

17. The decorative glass article of claim 16, wherein the glass article exhibits an L* value of less than or equal to 30 in the area where the decorative layer is disposed.

18. The decorative glass article of claim 17, wherein the glass article exhibits an L* value of less than or equal to 10 in the region where the polymeric material is present in the plurality of pores.

19. The decorated glass article according to any one of claims 17 to 18, wherein when light from a D65 illumination source is reflected from the glass substrate, the light exhibits a maximum ΔE value calculated using the CIE76 formula and between two different locations of the glass article where the decorative layer is disposed that is less than or equal to 3.

0.

20. A decorative glass product, comprising: The glass substrate comprises less than or equal to 55×10 -7 K -1 a coefficient of thermal expansion ("CTE") of , a first major surface, and a second major surface disposed opposite the first major surface; as well as A decorative layer adhered to at least a portion of the second major surface, the decorative layer comprising: Glass flux matrix, a plurality of low CTE additive component particles, and A plurality of holes, wherein: The decorative layer comprises greater than 15% by weight of the low CTE additive component particles, Each of the plurality of low CTE additive component particles comprises less than or equal to 10×10 -7 K -1 CTE, and The decorative layer includes a CTE of 15×10 -7 K -1 CTE within.

21. The decorative glass article of claim 20, wherein the decorative glass article has a probability of breakage of less than 10% when subjected to a ring-to-ring test with a ring diameter of 32 mm under a load of 60 MPa.

22. The decorative glass article of any one of claims 20 to 21, wherein the CTE of the decorative layer is less than or equal to 55×10 -7 K -1 .

23. The decorative glass article of any one of claims 20-22, wherein each of the plurality of low CTE additive component particles comprises glass, glass frit, glass enamel, ceramic enamel, glass ceramic, or a ceramic material.

24. The decorative glass article of any one of claims 20-23, wherein the decorative layer comprises greater than or equal to 20 wt% and less than or equal to 40 wt% of the low CTE additive component particles.

25. The decorated glass article of any one of claims 20-25, wherein the decorative layer comprises greater than or equal to 5 wt% and less than or equal to 30 wt% pigment.

26. The decorative glass article of any one of claims 20-25, wherein the decorative glass article exhibits an L* value according to the CIELAB color coordinate system of less than 15.0 when illuminated from the first major surface using a D65 illumination source.

27. The decorative glass article according to any one of claims 20 to 26, wherein the decorative glass article exhibits an integrated visible light transmittance of less than or equal to 2.0% for light of 400 nm to 700 nm normally incident on the first major surface in the region where the decorative layer covers the second major surface.

28. The decorated glass article of any one of claims 20-27, wherein the decorative layer comprises an average thickness of less than or equal to 20 μm.

29. The decorative glass article of any one of claims 20-28, wherein at least one of the plurality of pores comprises a maximum diameter greater than 1.0 μm.

30. The decorated glass article of any one of claims 20-29, wherein the decorative layer has a porosity of at least 15%.